Improved electrochemical separator
Patent Information
- Application Number
- CN202180051185.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-19
- Filing Date
- 2021-08-18
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-08-18
AI Technical Summary
[0011]发明人努力解决上文所提及的问题
[0101]提供具有高度耐穿刺性的复合膜降低了由于如果电池装配时复合膜被刺穿的情况下发生的短路所导致的电池失效的可能性。这还可以经由降低短路发生概率增加由所述复合膜制造的电化学装置的寿命。此外,在不增加复合膜厚度的情况下提供对于被其他电化学装置组件刺穿具有高度抗性的复合膜实现了使得复合膜保留了高的离子传导并且降低了制造成本,因为薄的复合膜需要较低含量的离聚物,具有相当比例的加固。
Smart Images

Figure CN116324041B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to polymer electrolyte membranes, and more specifically, to composite membranes having at least two reinforcing layers comprising a microporous polymer structure and surprisingly high puncture resistance. Background Technology
[0002] Polymer electrolyte membranes (PEMs) are a key component in many applications, such as fuel cells, electrolyzers, and redox flow cells.
[0003] In a fuel cell, the polymer electrolyte membrane (PEM) is a component of the membrane electrolyte assembly (MEA). The MEA is the core component of the fuel cell, where electrochemical reactions occur to generate energy. A typical MEA consists of: the PEM, two catalyst layers (i.e., the anode and cathode, which are attached to opposite sides of the PEM), and two gas diffusion layers (GDL) (attached to the two outer surfaces of the catalyst layers). The PEM separates the two reactant gas streams. On the anode side of the MEA, fuel (e.g., hydrogen) is oxidized and separated into electrons and protons. The cell is designed such that electrons move through an external circuit while protons migrate through the PEM. On the cathode side, electrons and protons react with an oxidant (i.e., oxygen or air) to produce water and heat. In this way, an electrochemical potential is maintained, and current can be obtained from the fuel cell for useful work.
[0004] Redox flow batteries utilize two soluble redox pairs as electroactive materials to store energy via oxidation and reduction reactions. Typically, a redox flow battery comprises two electrolyte reservoirs (cathiolyte and anode electrolyte), from which a pump circulates the electrolyte through an electrochemical cell stack. The cell stack typically comprises multiple cells connected in series or parallel, enabling electrochemical reactions to occur at inert electrodes. Each cell in the stack includes an anode, a cathode, and an ion-exchange membrane separator (e.g., a polymer electrolyte membrane, PEM) to allow ion diffusion through the membrane separator while preventing mixing of electrolyte solutions from both reservoirs.
[0005] An electrolyzer hydrolyzes water to produce hydrogen and oxygen. The reaction that occurs in an electrolyzer is very similar to that in a fuel cell, except that the processes at the anode and cathode are reversed. In a fuel cell, hydrogen is consumed at the anode, while in an electrolyzer, hydrogen is produced at the cathode. Bipolar electrolyzers (or PEM electrolyzers) use the same type of electrolyte separator as PEM fuel cells. The electrolyte separator is a thin, solid ion-conducting membrane that replaces the thick, porous membrane used in alkaline electrolyzers to separate the aqueous solution.
[0006] In PEMs, high selectivity (via high conductivity and / or low permeability), high durability, and low cost are all desirable qualities. However, in practical engineering, conflicts often arise when optimizing these properties, requiring trade-offs. Selectivity can be improved by increasing conductivity through reducing membrane thickness. Thinner PEMs are manufactured to reduce costs because ionomers are expensive and used less frequently. However, thinner membranes have increased hydrogen permeation, which erodes any selectivity gain from increased proton conduction and results in thinner membranes having similar or worse selectivity than thicker ones. Furthermore, thinner membranes are also more fragile and typically lack sufficient mechanical durability to withstand harsh automotive conditions. Reducing the physical thickness of the membrane also increases the probability of damage or puncture from other electrochemical device components, leading to shorter cell life.
[0007] In redox flow cells (RFB) employing electrode layers arranged on either side of the PEM, PEM puncture is particularly problematic. RFB electrode layers typically comprise porous layers (typically with pore sizes of 1-200 micrometers). These porous layers can contain felt, paper, or woven materials. RFB electrodes, often composed of carbon fibers, press against the PEM after the electrode layers are pressed during PEM electrode assembly, potentially puncturing the PEM. Therefore, the puncture resistance requirements of the membrane limit the availability of membranes with high proton conductivity.
[0008] Ultimately, pinholes that form and propagate through the polymer electrolyte membrane can cause PEM electrochemical devices to fail. Furthermore, these devices will also fail if current flows through the PEM (causing a short circuit in the system).
[0009] Existing techniques attempting to improve the mechanical resistance and puncture resistance of polymer electrolyte membranes (PEMs) involve reinforcing the membrane with a continuous layer of microporous polymer structure. This microporous polymer structure layer is achieved by incorporating a polymer electrolyte (e.g., an ionomer) and is therefore fully conductive to ions. However, even reinforced PEMs can be punctured after assembly during the manufacturing process of electrochemical devices.
[0010] Therefore, there is a demand for thin composite films that retain high performance and low ion resistance while exhibiting higher puncture resistance and subsequent short-circuit resistance to electrochemical device components compared to existing composite films. Summary of the Invention
[0011] The inventors have worked to address the problems mentioned above. They unexpectedly discovered that, for a given total content of microporous polymer structure and composite membrane thickness at 0% RH, distributing the microporous polymer structure within at least two (or more) reinforcing layers further increases the resistance of the electrochemical device components to membrane puncture during device fabrication. The inventors also found that the mean failure pressure of the composite electrolyte membrane is further improved as the total content of the microporous polymer structure (distributed between at least two reinforcing layers) increases. These findings are highly advantageous because the composite membrane described herein exhibits superior resistance to puncture of components in the electrochemical device in which the composite membrane is integrated compared to prior art composite electrolyte membranes. The inventors also unexpectedly discovered that separating the at least two reinforcing layers by at least a distance d further increases the composite membrane's resistance to puncture of components in the electrochemical device after device fabrication. Therefore, the composite membrane described herein exhibits superior resistance to puncture of electrochemical device elements after device fabrication without compromising membrane performance.
[0012] In one aspect, a composite membrane for an electrochemical device is provided, comprising:
[0013] a) at least two reinforcing layers, each of the at least two reinforcing layers comprising a microporous polymer structure; and
[0014] b) An ion exchange material (IEM) that is at least partially impregnated in the microporous polymer structure of the at least two reinforcing layers and thereby occlusive the microporous polymer structure; wherein the composite membrane has a thickness of at least 10 μm at 0% RH.
[0015] In the context of this disclosure, the term composite membrane includes polymer electrolyte membranes (PEMs) and composite electrolyte membranes.
[0016] The microporous polymer structure is present in the composite membrane at a total content (or amount) of at least about 20% by volume, based on the total volume of the composite membrane. In the context of this disclosure, the total content of the microporous polymer structure in the composite membrane is the total content (by mass or volume) of the microporous polymer structure present in the composite membrane (distributed among at least two reinforcing layers). In the context of this disclosure, the total content of the microporous polymer structure in the composite membrane can also be expressed as the content of reinforcing microporous polymer structures in the composite membrane.
[0017] Composite membranes may include two reinforcing layers. Composite membranes may include three reinforcing layers. Composite membranes may include four reinforcing layers. Composite membranes may include five reinforcing layers. Composite membranes may include two to ten reinforcing layers. Composite membranes may include any suitable number of reinforcing layers.
[0018] The composite membrane can have a thickness of at least about 10 μm at 0% relative humidity (RH). Specifically, the composite membrane can have the following thicknesses at 0% relative humidity (RH): about 10 μm to about 115 μm, or about 10 μm to about 100 μm, or about 10 μm to about 90 μm, or about 10 μm to about 80 μm, or about 10 μm to about 75 μm, or about 10 μm to about 70 μm, or about 10 μm to about 60 μm, or about 10 μm to about 50 μm, or about 10 μm to about 40 μm, or about 10 μm to about... 30 μm, or about 10 μm to about 20 μm, or about 10 μm to about 15 μm, or about 10 μm to about 12 μm, or about 20 μm to about 60 μm, or about 30 μm to about 60 μm, or about 40 μm to about 60 μm, or about 12 μm to about 30 μm, or about 12 μm to about 20 μm, or about 15 μm to about 30 μm, or about 15 μm to about 20 μm, or about 20 μm to about 30 μm. The composite membrane can have the following thicknesses at 0% RH: approximately 10 μm, or approximately 11 μm, or approximately 12, or approximately 13 μm, or approximately 14 μm, or approximately 15 μm, or approximately 16 μm, or approximately 17 μm, or approximately 18 μm, or approximately 19 μm, or approximately 20 μm, or approximately 21 μm, or approximately 22 μm, or approximately 23 μm, or approximately 24 μm, or approximately 25 μm, or approximately 30μm, or about 35μm, or about 40μm, or about 45μm, or about 50μm, or about 55μm, or about 60μm, or about 65μm, or about 70μm, or about 75μm, or about 80μm, or about 85μm, or about 90μm, or about 95μm, or about 100μm, or about 105μm, or about 110μm, or about 115μm.
[0019] In the context of this disclosure, the total content of the microporous polymer structure within the composite membrane can be presented as follows: the total mass per unit area of the microporous polymer structure in the composite membrane (distributed between at least two reinforcing layers) (g / m²). 2The composite membrane may include one or more types of microporous polymer structures. For example, the composite membrane may include a single type of microporous polymer structure (e.g., ePTFE) present in at least two reinforcing layers. The composite membrane may include at least two reinforcing layers, and each reinforcing layer may include a mixture of different types of microporous polymer structures (e.g., fluorinated polymers and hydrocarbon polymers). The composite membrane may include at least two reinforcing layers, and the first of the at least two reinforcing layers may include a single type of microporous polymer structure (e.g., ePTFE), while the second of the at least two reinforcing layers may include a single type of microporous polymer structure (e.g., a hydrocarbon polymer) different from the microporous polymer structure of the first of the at least two reinforcing layers. The total content of microporous polymer structures in the composite membrane, expressed as mass per unit area (i.e., the total mass of microporous polymer structures present in each reinforcing layer of the composite membrane divided by the area of the composite membrane), can be standardized using the following equation:
[0020]
[0021] Among them, M mps This refers to the mass (g) of the microporous polymer structure, A 复合膜 It is the total area of the composite membrane (m²) 2 ), matrix skeleton density mps This refers to the matrix framework density (g / cm³) of the microporous polymer structure. 3 ).
[0022] Matrix skeleton density is the solid mass divided by the volume of solid excluding open and closed pores. Matrix skeleton density represents the density of the solid portion of a material, and therefore its unit is grams of solids per cubic centimeter (g / cm³). 3 Solid. Matrix skeleton density is typically assessed experimentally using the helium gravity method and represents the true solid density of the material without closed porosity. For non-porous solids, matrix skeleton density is the same as geometric density or envelope density. In the context of this disclosure, the matrix skeleton density of ePTFE can be approximately 2.25 g / cm³. 3 The matrix skeleton density of track-etched porous polycarbonate can be approximately 1.20 g / cm³. 3 .
[0023] In embodiments where the composite membrane comprises more than one type of microporous polymer structure, the normalized total content (in mass / area) of the microporous polymer structure in the composite membrane can be calculated using the following equation:
[0024]
[0025] Wherein, mps1 is microporous polymer structure 1 (e.g., ePTFE), mps2 is microporous polymer structure 1 (e.g., polycarbonate), and mpsN is microporous polymer structure N (if N different types of microporous polymer structures exist in the composite membrane).
[0026] The normalized total content of the microporous polymer structure in the composite membrane can be at least about 2.4 × 10⁻⁶. -6 m (i.e., 2.4 μm), or about 3 μm, or about 3.5 μm, or about 4 μm, or about 4.5 μm, or about 5 μm, or about 5.5 μm, or about 6 μm, or about 6.5 μm, or about 7 μm, or about 8 μm, or about 8.5 μm, or about 9 μm, based on the total area of the composite membrane.
[0027] As discussed above, the total content of microporous polymer structures in the composite membrane can be expressed as the volume percentage of the composite membrane occupied by microporous polymer structures (distributed between at least two reinforcing layers). The total content of the present microporous polymer structures can be: at least about 15% by volume, or at least about 20% by volume, or at least about 25% by volume, or at least about 30% by volume, or at least about 35% by volume, or at least about 40% by volume, or at least about 45% by volume, or at least about 50% by volume, or at least about 55% by volume, or at least about 60% by volume, or at least about 65% by volume, or at least about 70% by volume, based on the total volume of the composite membrane.
[0028] The total content of the present microporous polymer structure may be: about 15 vol% to about 70%, or about 20 vol% to about 70%, or about 30 vol% to about 70%, or about 40 vol% to about 70%, or about 50 vol% to about 70%, or about 60 vol% to about 70%, or about 65 vol% to about 70%, or about 15 vol% to about 65%, or about 20 vol% to about 65%, or about 30 vol% to about 65%, about 40 vol% to about 65%, or about 50 vol% to about 65%, or about 60 vol% to about 65%, or about 20 vol% to about 60%, or about 20 vol% to about 50%, or about 20 vol% to about 40%, or about 20 vol% to about 30%, or about 40 vol% to about 60%, or about 40 vol% to about 50%, based on the total volume of the composite membrane. The total content of the existing microporous polymer structure can be: about 20% by volume, or about 25% by volume, or about 30% by volume, or about 35% by volume, or about 40% by volume, or about 45% by volume, or about 50% by volume, or about 55% by volume, or about 60% by volume, or about 65% by volume, based on the total volume of the composite membrane.
[0029] The composition of the at least two reinforcing layers can be the same. Alternatively, the composition of the at least two reinforcing layers can be different.
[0030] Microporous polymer structures may include fluorinated polymers. These structures may include one or more fluorinated polymers selected from the group consisting of polytetrafluoroethylene (PTFE), poly(ethylene cotetrafluoroethylene) (EPTFE), expanded polytetrafluoroethylene (ePTFE), polyvinylidene fluoride (PVDF), expanded polyvinylidene fluoride (ePVDF), expanded poly(ethylene cotetrafluoroethylene) (eEPTFE), or mixtures thereof. Preferably, the fluorinated polymer may be perfluorinated expanded polytetrafluoroethylene (ePTFE).
[0031] Microporous polymer structures can contain hydrocarbon polymers. Hydrocarbon polymers can include polyethylene, polypropylene, polycarbonate, track-etched polycarbonate, polystyrene, or mixtures thereof.
[0032] In embodiments where the microporous polymer structure includes ePTFE, the total mass per unit area of the microporous polymer structure can be at least about 5.5 g / m³. 2 or at least about 6g / m 2 or at least about 7g / m 2 or at least about 8g / m 2 or at least about 9g / m 2 or at least about 10g / m 2 or at least about 11g / m 2 or at least about 12g / m 2 or at least about 14g / m 2 or at least about 16g / m 2 Based on the total area of the composite membrane.
[0033] In embodiments where the microporous polymer structure includes ePTFE, the total mass per unit area of the microporous polymer structure can be approximately 5.5 g / m³. 2 Approximately 80g / m 2 Or approximately 5.5g / m 2 Approximately 70g / m 2 Or approximately 5.5g / m 2 Approximately 60g / m 2 Or approximately 5.5g / m 2 Approximately 60g / m 2 Or approximately 5.5g / m 2 Approximately 50g / m 2 Or approximately 5.5g / m 2 Approximately 40g / m 2 Or approximately 5.5g / m 2 Approximately 35g / m2 Or approximately 5.5g / m 2 Approximately 30g / m 2 Or approximately 5.5g / m 2 Approximately 20g / m 2 Or approximately 5.5g / m 2 Approximately 15g / m 2 Based on the total area of the composite membrane.
[0034] When the composite membrane is used in redox flow cell applications, preferably, the total mass per unit area of the microporous polymer structure can be approximately 5.5 g / m³. 2 Approximately 35g / m 2 Or approximately 5.5g / m 2 Approximately 16g / m 2 Or approximately 5.5g / m 2 Approximately 14g / m 2 Or approximately 5.5g / m 2 Approximately 12g / m 2 Or approximately 5.5g / m 2 Approximately 10g / m 2 or about 9g / m 2 Approximately 20g / m 2 or about 9g / m 2 Approximately 15g / m 2 or about 10g / m 2 Approximately 18g / m 2 or about 8g / m 2 Approximately 15g / m 2 It is calculated based on the sum of the unit area mass of all microporous layers present in the composite membrane.
[0035] When composite membranes are used in electrolyzer applications, the content of microporous polymer structures can be higher than in redox flow cell applications. For example, when composite membranes are used in electrolyzer applications, the total mass per unit area of the microporous polymer structure can be approximately 20 g / m³. 2 Approximately 80g / m 2 or about 30g / m 2 Approximately 70g / m 2 or about 20g / m 2 Approximately 50g / m 2 or about 30g / m 2 Approximately 60g / m 2 It is calculated based on the sum of the unit area mass of all microporous layers present in the composite membrane.
[0036] In embodiments where the microporous polymer structure includes ePTFE, the total mass per unit area of the microporous polymer structure can be approximately 5.5 g / m³.2 or about 6g / m 2 or about 7g / m 2 or about 8g / m 2 or about 9g / m 2 or about 10g / m 2 or about 11g / m 2 or about 12g / m 2 or about 13g / m 2 or about 14g / m 2 or about 15g / m 2 or about 16g / m 2 or about 17g / m 2 or about 18g / m 2 or about 19g / m 2 or about 20g / m 2 It is calculated based on the sum of the unit area mass of all microporous layers present in the composite membrane.
[0037] In embodiments where the microporous polymer structure includes hydrocarbon polymers, the total mass per unit area of the microporous polymer structure can be at least about 3.5 g / m³. 2 or at least about 4g / m 2 Or at least about 4.5g / m 2 or at least about 5g / m 2 or at least approximately 5.5g / m 2 or at least about 6g / m 2 or at least about 7g / m 2 or at least about 8g / m 2 Based on the total area of the composite membrane.
[0038] When measured by the average puncture pressure failure test described below, the composite membrane may have the following average failure pressure: at least about 150 psi, or at least about 160 psi, or at least about 170 psi, or at least about 180 psi, or at least about 190 psi, or at least about 200 psi.
[0039] When measured by the mean puncture pressure failure test described below, the composite membrane may have the following mean failure pressures: about 150 psi to about 2000 psi, or about 150 psi to about 1500 psi, or about 150 psi to about 1000 psi, or about 150 psi to about 500 psi, or about 150 psi to about 300 psi, or about 200 psi to about 400 psi, or about 200 psi to about 400 psi.
[0040] When measured by the average puncture pressure failure test described below, the composite membrane may have the following average failure pressure: approximately 150 psi, or approximately 200 psi, or approximately 250 psi, or approximately 300 psi, or approximately 350 psi, or approximately 400 psi, or approximately 450 psi, or approximately 500 psi.
[0041] The at least two reinforcing layers may be in direct contact. Alternatively, the at least two reinforcing layers may not be in direct contact with each other. The at least two reinforcing layers may be separated by a distance d. In embodiments where the at least two reinforcing layers are in direct contact, the distance d may be approximately 0 μm. The distance d can be: about 0.1 μm to about 20 μm, or about 0.1 μm to about 15 μm, or about 0.1 μm to about 10 μm, or about 10 μm to about 20 μm, or about 10 μm to about 15 μm, or about 15 μm to about 20 μm, or about 2 μm to about 8 μm, or about 2 μm to about 6 μm, or about 2 μm to about 4 μm, or about 4 μm to about 8 μm, or about 6 μm to about 8 μm, or about 3 μm to about 6 μm, or about 0.5 μm to about 10 μm, or about 1 μm to about 10 μm, or about 4 μm to about 6 μm, or about 1 μm to about 5 μm, or about 5 μm to about 10 μm. The distance d can be: approximately 0.1 μm, or approximately 0.5 μm, or approximately 1 μm, or approximately 2 μm, or approximately 3 μm, or approximately 4 μm, or approximately 5 μm, or approximately 6 μm, or approximately 7 μm, or approximately 8 μm, or approximately 9 μm, or approximately 10 μm, or approximately 11 μm, or approximately 12 μm, or approximately 13 μm, or approximately 14 μm, or approximately 15 μm, or approximately 16 μm, or approximately 17 μm, or approximately 18 μm, or approximately 19 μm, or approximately 20 μm.
[0042] The at least two reinforcing layers may be separated by at least one layer of ion exchange material (IEM). Each layer of the at least one ion exchange material may contain a single ion exchange material. Each layer of the at least one ion exchange material may contain a mixture of two or more ion exchange materials. Each layer of the at least one ion exchange material may contain at least one ionomer. The at least one ionomer may include a proton-conducting polymer. The proton-conducting polymer may include a hydrocarbon ionomer. The proton-conducting polymer may include a perfluorinated ionomer. The proton-conducting polymer may include perfluorosulfonic acid. Each layer of the at least one ion exchange material may be about 1 μm to about 10 μm thick. The ion exchange material may have the following equivalent volumes: about 240 cc / mol equivalent to about 870 cc / mol equivalent, or about 240 cc / mol equivalent to about 650 cc / mol equivalent, or about 350 cc / mol equivalent to about 475 cc / mol equivalent. At 0% relative humidity, the ion exchange material may have a density of not less than about 1.9 g / cc.
[0043] The at least two reinforcing layers may be separated by a layer of ion exchange material (IEM). The ion exchange material layer may contain a single ion exchange material. The ion exchange material layer may contain a mixture of more than one ion exchange material.
[0044] The at least two reinforcing layers may be separated by two or more layers of ion exchange material. At least two of the two or more layers of ion exchange material may contain different ion exchange materials. At least two of the two or more layers of ion exchange material may contain the same ion exchange material.
[0045] The at least two reinforcing layers may be separated by an ion exchange material (IEM) layer, wherein the ion exchange material comprises more than one layer of ion exchange material, and wherein the ion exchange material layer disposed between the at least two reinforcing layers is formed of different ion exchange materials.
[0046] Each of the at least two reinforcing layers may have a first surface and a second surface, and at least one or both of the first and second surfaces of each reinforcing layer may be at least partially impregnated with an ion exchange material.
[0047] In an embodiment where the composite membrane comprises two reinforcing layers, the first reinforcing layer may include a first surface and a second surface, and the second reinforcing layer may also include a first surface and a second surface. The first surfaces of both the first and second reinforcing layers may be at least partially impregnated with an ion exchange material. The second surfaces of both the first and second reinforcing layers may also be at least partially impregnated with an ion exchange material.
[0048] In embodiments where both the first surface of the first reinforcing layer and the second surface of the second reinforcing layer are at least partially impregnated with ion exchange material, the ion exchange material on the first surface of the first reinforcing layer and the ion exchange material on the second surface of the second reinforcing layer may be the same or different.
[0049] The microporous polymer structure can at least partially absorb ion exchange material. The microporous polymer structure can completely absorb ion exchange material. In embodiments where the composite membrane has two reinforcing layers, the microporous polymer structure of the two reinforcing layers can completely absorb ion exchange material. Furthermore, the composite membrane may include two additional ion exchange material layers on its first and second surfaces. Additionally, the first and second reinforcing layers may be separated from each other via another (internal) ion exchange material layer. In one embodiment, the at least two reinforcing layers may be separated from each other via another (internal) ion exchange material layer, forming a spacing d. The ion exchange material layers disposed on the first surface of the composite membrane, the second surface of the composite membrane, and / or between the two reinforcing layers may contain the same or different ion exchange materials. For example, the ion exchange material may be an ionomer.
[0050] In embodiments where at least one layer of a microporous polymer structure in the reinforcing layer at least partially absorbs ion exchange material, the ion exchange material may leave an unocclusive portion of the microporous polymer structure at a first surface, a second surface, or both surfaces closest to the reinforcing layer. The unocclusive portion may be a portion of the microporous polymer structure that does not contain any ion exchange material. Alternatively, the unocclusive portion may be a portion of the microporous polymer structure that includes a coating of ion exchange material on the inner surface of the microporous polymer structure, but without ion exchange material on the outer surface of the microporous polymer structure (i.e., the composite membrane does not contain any layer of non-reinforcing ion exchange material, but may contain a coating of ion exchange material coated with the internal filaments of the microporous polymer structure).
[0051] The total average equivalent volume of the ion exchange material can be from approximately 240 cc / mol equivalent to approximately 870 cc / mol equivalent. The average equivalent volume of the ion exchange material can be from approximately 240 cc / mol equivalent to approximately 650 cc / mol equivalent. The average equivalent volume of the ion exchange material can be from approximately 350 cc / mol equivalent to approximately 475 cc / mol equivalent. The total average equivalent volume of the ion exchange material can include the total volume of the ion exchange material distributed between all the ion exchange material layers of the composite membrane.
[0052] Ion exchange materials can have approximately 400 g / equivalent to approximately 2000 g / equivalent SO3. -Total equivalent weight (EW). Ion exchange materials can have approximately 470 g / equivalent to approximately 1275 g / equivalent SO3. - Total equivalent weight (EW). Ion exchange materials can have approximately 700 g / equivalent to approximately 1000 g / equivalent SO3. - Total equivalent weight (EW). Ion exchange materials can have approximately 710 g / equivalent SO3. - The equivalent weight. Ion exchange materials can have approximately 810 g / equivalent SO3. - The equivalent weight. Ion exchange materials can have approximately 910 g / equivalent SO3. - The equivalent weight.
[0053] In embodiments where the composite membrane includes two reinforcing layers arranged in direct contact, the second surface of the first reinforcing layer and the first surface of the second reinforcing layer can be in direct contact.
[0054] In embodiments where the composite membrane comprises two reinforcing layers arranged separately from each other, the second surface of the first reinforcing layer and the first surface of the second reinforcing layer may be separated by a distance d via an ion exchange material layer (i.e., the inner layer of the ion exchange material). The inner layer of the ion exchange material may have a thickness d.
[0055] The composite membrane may include a first surface and a second (opposite) surface. The first surface of the composite membrane may contain a first ion exchange material. The second surface of the composite membrane may contain a second ion exchange material. The composite membrane may include at least one inner layer of ion exchange material between the at least two reinforcing layers.
[0056] In embodiments where the composite membrane comprises three or more reinforcing layers, all reinforcing layers may be in direct contact with each other. Alternatively, some reinforcing layers may be in direct contact with each other, while others may be separated from each other (e.g., via layers of ion exchange material). Alternatively, all reinforcing layers may be separated from each other. In embodiments comprising reinforcing layers that are separated from each other, the reinforcing layers may be separated from each other via ion exchange material. For example, the composite membrane may comprise three or more reinforcing layers, each reinforcing layer being separated from the next reinforcing layer via one or more layers of ion exchange material. Furthermore, the outer reinforcing layers may be at least partially impregnated with ion exchange material on their outer surfaces.
[0057] The composite membrane may contain at least one ion exchange material on each of its outer surfaces. Furthermore, the composite membrane may contain an inner layer of at least one ion exchange material between the at least two reinforcing layers. The at least one ion exchange material may be an unreinforced ion exchange material. In the context of this disclosure, an unreinforced ion exchange material can be a layer of ion exchange material that is substantially not embedded in the reinforcing layers. In other words, in a composite membrane having one or more reinforcing layers, the unreinforced ion exchange material is an ion exchange material layer present in some location within the composite membrane (e.g., on the outer surface or as an inner layer), but which is substantially not embedded (or absorbed) into the one or more reinforcing layers.
[0058] The composite membrane may also include a backing layer disposed on a first surface, a second surface, or both of the composite membrane. A suitable backing layer may include at least one support structure, which may comprise a woven material, such as: linen made of expanded porous polytetrafluoroethylene woven fibers; a mesh made of extruded or oriented polypropylene or polypropylene mesh, commercially available from Conwed, Inc., Minneapolis, Minnesota; and woven materials of polypropylene and polyester from Tetko, Inc., Briarcliff Manor, New York. Suitable nonwoven materials may include, for example, spunbond polypropylene from Reemay, Inc., Old Hickory, Tennessee. In other respects, the support structure may include a mesh made of materials such as polyethylene (“PE”), polystyrene (“PS”), cyclic olefin copolymer (“COC”), cyclic olefin polymer (“COP”), fluorinated ethylene propylene (“FEP”), perfluoroalkoxyalkane (“PFA”), ethylene tetrafluoroethylene (“ETFE”), polyvinylidene fluoride (“PVDF”), polyetherimide (“PEI”), polysulfone (“PSU”), polyethersulfone (“PES”), polyphenylene oxide (“PPO”), polyphenylene ether (“PPE”), polymethylpentene (“PMP”), polyethylene terephthalate (“PET”), or polycarbonate (“PC”). In some aspects, the support structure may also include a protective layer, which may comprise: polyethylene (PE), polystyrene (“PS”), cyclic olefin copolymer (“COC”), cyclic olefin polymer (“COP”), fluorinated ethylene propylene (“FEP”), perfluoroalkoxyalkane (“PFA”), ethylene tetrafluoroethylene (“ETFE”), polyvinylidene fluoride (“PVDF”), polyetherimide (“PEI”), polysulfone (“PSU”), polyethersulfone (“PES”), polyphenylene oxide (“PPO”), polyphenylene ether (“PPE”), polymethylpentene (“PMP”), polyethylene terephthalate (“PET”), or polycarbonate (“PC”). The support structure may optionally include a reflective layer comprising a metallic substrate (e.g., an aluminum substrate). The choice of specific metal can be wide-ranging, as long as it is reflective. A non-limiting list of exemplary metals includes: aluminum, beryllium, cerium, chromium, copper, germanium, gold, hafnium, manganese, molybdenum, nickel, platinum, rhodium, silver, tantalum, titanium, tungsten, zinc, or alloys (e.g., Inconel or bronze). The reflective layer optionally comprises a mixture or alloy of two or more metals (optionally, the two or more metals listed above). The reflective layer may optionally comprise a high-reflectivity polymer multilayer film, such as the Vikuiti™ enhanced specular reflector available from 3M. In another example, the reflective layer may optionally comprise a high-reflectivity nonmetallic inorganic dielectric multilayer film containing materials such as: magnesium fluoride, calcium fluoride, titanium dioxide, and silicon dioxide.
[0059] In another aspect, a membrane electrode assembly for an electrochemical device is provided, comprising:
[0060] At least one electrode; and
[0061] The composite membrane described above is in contact with the at least one electrode.
[0062] The composite film can be attached to the at least one electrode. The composite film can be adhered to the at least one electrode. The composite film can be attached to the at least one electrode. The composite film can be pressed against the at least one electrode. The composite film can be fused to the at least one electrode.
[0063] The at least one electrode may include fibers. The at least one electrode may be a fibrous electrode. The at least one electrode may be doped with fibers. The at least one electrode may include carbon fibers. The at least one electrode may include a porous layer (typically with a pore size of 1-200 micrometers). The porous layer may comprise felt, paper, or woven materials, etc.
[0064] The membrane electrode assembly can be a redox flow cell membrane electrode assembly, which includes:
[0065] First electrode; second electrode; and
[0066] The composite membrane as described above is sandwiched between the first electrode and the second electrode.
[0067] The membrane electrode assembly can be a redox flow cell membrane electrode assembly, which includes:
[0068] A first electrode having a first surface and a second surface;
[0069] A second electrode having a first surface and a second surface; and
[0070] As described above, a composite film having a first surface and a second surface,
[0071] The second surface of the first electrode is in contact with the first surface of the composite film, and the first surface of the second electrode is in contact with the second surface of the composite film.
[0072] The first electrode may be a first electrode layer, and the second electrode may be a second electrode layer. A redox flow cell membrane electrode assembly may include a first electrode layer attached to a first surface of a composite membrane and a second electrode layer attached to a second surface of the composite membrane. The electrode may be a porous layer with a pore size of about 1 to about 200 μm. The electrode may be selected from felt, paper, or woven materials. The electrode may include doped carbon fibers.
[0073] The membrane electrode assembly can be a fuel cell membrane electrode assembly, which includes:
[0074] The composite membrane described above has a first surface and a second surface.
[0075] The first layer of electrode catalyst adhered to the first surface of the composite membrane; and
[0076] The second layer of electrode catalyst adheres to the second surface of the composite membrane.
[0077] The fuel cell membrane electrode assembly may also include a fluid diffusion layer. The fluid diffusion layer may be a gas diffusion layer and / or a liquid (e.g., water) diffusion layer. The fluid diffusion layer may be disposed on the outer surface of a first layer and / or a second layer of the electrode catalyst. The fuel cell membrane electrode assembly may include:
[0078] The composite membrane described above has a first surface and a second surface.
[0079] A first layer of electrode catalyst adhered to the first surface of the composite membrane, and a first fluid diffusion layer disposed on the first layer of electrode catalyst; and
[0080] The second layer of electrode catalyst adhered to the second surface of the composite membrane, and the second fluid diffusion layer disposed on the second layer of electrode catalyst.
[0081] In a fuel cell membrane electrode assembly, a first fluid diffusion layer can be arranged opposite to the composite membrane. A first layer of electrode catalyst can be arranged between the composite membrane and the first fluid diffusion layer. Secondly, the first fluid diffusion layer can be arranged opposite to the composite membrane. A second layer of electrode catalyst can be arranged between the composite membrane and the second fluid diffusion layer. In other words, the first and second fluid diffusion layers can be the outermost layers of the fuel cell membrane electrode assembly, and they can be sandwiched between the composite membrane and the first and second layers of electrode catalyst.
[0082] In a fuel cell membrane electrode assembly, the first and second layers of the electrode catalyst can be nanoporous layers with a pore size of up to about 100 nm. The first and second electrode catalyst layers are adhered to the composite membrane. The first layer of the electrode catalyst can be an anode, and the second layer of the electrode catalyst can be a cathode.
[0083] In a fuel cell membrane electrode assembly, the first and second layers of the electrode catalyst may comprise:
[0084] One or more ionomers;
[0085] Catalyst support, such as carbon black; and
[0086] platinum.
[0087] The membrane electrode assembly can be an electrolyzer electrode assembly, which includes:
[0088] The composite membrane described herein has a catalyst layer stacked on the composite membrane;
[0089] Electrodes; and
[0090] A gas diffusion layer is arranged between the composite membrane and the electrode.
[0091] The membrane electrode assembly can be an electrolyzer electrode assembly, which includes:
[0092] The composite membrane described above has a first surface and a second surface.
[0093] The first layer of electrode catalyst adhered to the first surface of the composite membrane; and
[0094] A second layer of electrode catalyst is adhered to the second surface of the composite membrane. A fluid (e.g., gas / water) diffusion layer may be disposed on the outer surface of the electrode catalyst.
[0095] In another aspect, an electrochemical device comprising the composite membrane described above is provided. The electrochemical device may be a fuel cell, a redox flow cell, or an electrolyzer.
[0096] In another aspect, a fuel cell comprising a composite membrane or fuel cell membrane electrode assembly as described above is provided.
[0097] In another aspect, a redox flow cell comprising a composite membrane or redox flow cell membrane electrode assembly as described above is provided.
[0098] In another aspect, an electrolyzer comprising a composite membrane or electrolyzer membrane electrode assembly as described above is provided.
[0099] As described above, the inventors sought to address the problem of low puncture resistance in existing PEM technology. As a result, they unexpectedly discovered that increasing the content of reinforcing microporous polymer structures in the composite membrane (i.e., the total content of microporous polymer structures distributed between at least two reinforcing layers) consistently increases puncture resistance. Surprisingly, this increase in puncture resistance can be achieved without increasing the composite membrane thickness or the amount of ionomer used.
[0100] In addition, the inventors discovered that, for a given total amount of reinforced microporous polymer structure, providing the microporous polymer structure in a multilayer arrangement (at least two layers) of the reinforcing layer significantly improves the puncture resistance of the composite membrane (compared to polymer electrolyte membranes having an equivalent amount of microporous polymer structure provided in a single layer).
[0101] Providing a composite film with high puncture resistance reduces the likelihood of battery failure due to short circuits that occur if the composite film is punctured during battery assembly. This also increases the lifespan of electrochemical devices manufactured from the composite film by reducing the probability of short circuits. Furthermore, providing a composite film with high resistance to punctures by other electrochemical device components without increasing the composite film thickness allows the composite film to retain high ion conductivity and reduces manufacturing costs, as a thin composite film requires a lower content of ionomers and has a considerable proportion of reinforcement. Attached Figure Description
[0102] Figure 1A A schematic representative view of a cross-section of a composite membrane according to an embodiment of the present disclosure is shown. The composite membrane has two reinforcing layers in direct contact with each other. Each reinforcing layer comprises a microporous polymer structure. The composite membrane also includes two outer layers of unreinforced ion exchange materials. In this specific embodiment, both reinforcing membranes are impregnated with the same ion exchange material (however, in other examples, the reinforcing layers may be impregnated with different ion exchange materials).
[0103] Figure 1B Display with backing layer Figure 1A Composite membrane.
[0104] Figure 2 A schematic representative view showing a cross-section of a composite membrane according to another embodiment is shown. The composite membrane has the same characteristics as... Figure 1A and 1B The composite membrane has a similar structure, but the first reinforcing layer is impregnated with a first ion exchange material, and the second reinforcing layer is impregnated with a second (different) ion exchange material.
[0105] Figure 3A A schematic representative view showing a cross-section of a composite membrane according to an embodiment of the present disclosure. The composite membrane has two reinforcing layers, each containing a microporous polymer structure. The two reinforcing layers are separated by an inner unreinforced layer of ion exchange material. The composite membrane also includes two outer unreinforced ion exchange material layers on the outer surfaces of the reinforcing layers.
[0106] Figure 3B Display includes Figure 3A A schematic cross-sectional view of a redox flow cell membrane electrode assembly consisting of a composite membrane and two electrode layers.
[0107] Figure 4This schematic representation shows a cross-section of a composite membrane according to another embodiment of the present disclosure. The structure is similar to the membrane in FIG3 (having two reinforcing layers impregnated with ion exchange material, the reinforcing layers being separated by an inner layer of unreinforced ion exchange material disposed between the two reinforcing layers). This composite membrane has a single layer of unreinforced ion exchange material on the outer surface of one of the reinforcing layers, but no layer of unreinforced ion exchange material on the opposite side (i.e., on the outer surface of the other reinforcing layer).
[0108] Figure 5 A schematic representative view showing a cross-section of a composite membrane according to another embodiment of the present disclosure. This structure is similar to the membrane of FIG. 1, having two reinforcing layers in direct contact with each other, without an intervening unreinforced ion exchange material layer. In this example, the composite membrane has a single unreinforced ion exchange material layer on one outer side, but no unreinforced ion exchange material layer on the opposite side (i.e., the outer surface of one of the reinforcing layers is coated with a layer of unreinforced ion exchange material, but the outer surface of the other reinforcing layer is not coated with a layer of unreinforced ion exchange material).
[0109] Figure 6 A schematic representative view showing a cross-section of a composite membrane according to another embodiment of the present disclosure. This structure is similar to the membrane of FIG1, having two reinforcing layers in direct contact with each other, no intervening unreinforced ion exchange material layer, and an outer layer without unreinforced ion exchange material.
[0110] Figure 7 A schematic representative view showing a cross-section of a composite membrane according to another embodiment of the present disclosure. In this embodiment, the composite membrane has three reinforcing layers comprising microporous polymer structures impregnated with ion exchange materials. All three reinforcing layers are in direct contact with each other, and the composite membrane has two outer layers of unreinforced ion exchange materials disposed on opposite outer surfaces of the composite membrane.
[0111] Figure 8 A schematic representative view showing a cross-section of a composite membrane according to another embodiment of the present disclosure. In this embodiment, the composite membrane has three reinforcing layers, each reinforcing layer comprising a microporous polymer structure impregnated with an ion exchange material. The reinforcing layers are separated from each other by inner layers of unreinforced ion exchange material. The composite membrane has two outer layers of unreinforced ion exchange material on opposite outer surfaces of the composite membrane.
[0112] Figure 9 Display similar to Figure 6 A schematic representation of the composite membrane, having two reinforcing layers in direct contact with each other, one reinforcing layer completely absorbs the ion exchange material, while the other reinforcing layer absorbs the majority of the ion exchange material, but contains unabsorbed or unsealed areas containing microporous polymer structures.
[0113] Figure 10 The graph shown represents the relationship between the average failure pressure (psi) of the composite membrane and the total ePTFE content (MPa) of the composite membrane in the example. The graph displays data for four series, each with a comparable composite membrane thickness.
[0114] Figure 11 shows Table 1, which presents the properties of the composite membranes in the examples.
[0115] Figure 12 shows Table 2, which presents the properties of the microporous polymer structure in the composite membrane used in the examples.
[0116] Figure 13 The diagram shows a schematic representation of a composite membrane manufacturing method according to an embodiment of the present disclosure, having a reinforcing layer separated by an inner layer of ion exchange material (ionomer). Detailed Implementation
[0117] This application discloses a composite membrane for an electrochemical device that exhibits an improved mean failure pressure compared to prior art composite membranes. This results in improved puncture resistance of the composite membrane against other components of the electrochemical device after assembly. Not wishing to be limited by theory, providing a composite membrane with at least two reinforcing layers (each of which comprises a microporous polymer structure) significantly contributes to the improvement of the composite membrane's puncture resistance (compared to a composite membrane of similar thickness where the microporous polymer structure content is provided in a single reinforcing layer). Furthermore, for any given composite membrane thickness, increasing the total content of the microporous polymer structure distributed between two or more reinforcing layers further improves the composite membrane's puncture resistance. Not wishing to be limited by theory, for any given microporous polymer content and composite membrane thickness, providing separation between at least two reinforcing layers within the composite membrane can further improve the composite membrane's puncture resistance.
[0118] In some embodiments, a composite membrane for an electrochemical device is provided, comprising:
[0119] a) at least two reinforcing layers, each of the at least two reinforcing layers comprising a microporous polymer structure; and
[0120] b) An ion exchange material (IEM) that is at least partially absorbed into the microporous polymer structure of the at least two reinforcing layers and thereby closes the microporous polymer structure; wherein the composite membrane has a thickness of at least about 10 μm at 0% RH.
[0121] The implementation methods are described using volume-based numerical values, thereby providing a meaningful way to compare the compositions of composite membranes containing ionomers of different densities and microporous polymer structures.
[0122] To provide a meaningful numerical value for the content of microporous polymer structures within the composite membrane, rather than for values that are independent of the intrinsic molecular weight / matrix density of the microporous polymer structures, embodiments are described using standardized total mass per unit area. This takes into account that some embodiments may contain different microporous polymer structures in the reinforcing layer. Presenting the content of microporous polymer structures within the composite membrane as a mass per unit area is a suitable measurement for embodiments containing a single type of microporous polymer structure.
[0123] The microporous polymer structure can be present at a total content of at least about 20% by volume, based on the total volume of the composite membrane. The composite membrane can have a content of at least about 3.10. -6 The total microporous polymer structure content m (i.e., at least 3 μm) is based on the total area of the composite membrane divided by the matrix skeleton density of the microporous polymer structure.
[0124] The following provides the various definitions used in this disclosure.
[0125] As used herein, the terms "ionomer" and "ion exchange material" refer to cation exchange materials, anion exchange materials, or ion exchange materials that simultaneously possess cation and anion exchange capabilities. Mixtures of ion exchange materials may also be used. Ion exchange materials can be perfluorinated or hydrocarbon-based. Suitable ion exchange materials include, for example: perfluorosulfonic acid polymers, perfluorocarboxylic acid polymers, perfluorophosphonic acid polymers, styrene ion exchange polymers, fluorostyrene ion exchange polymers, polyaryletherketone ion exchange polymers, polysulfone ion exchange polymers, bis(fluoroalkylsulfonyl)imides, (fluoroalkylsulfonyl)(fluorosulfonyl)imides, polyvinyl alcohol, polyethylene oxide, divinylbenzene, metal salts containing or not containing polymers, and mixtures thereof. In an exemplary embodiment, the ion exchange material comprises a perfluorosulfonic acid (PFSA) polymer manufactured by copolymerizing (converting to proton form) tetrafluoroethylene and perfluorosulfonyl vinyl ester.
[0126] As used herein, the “equivalent weight” (EW) of an ionomer or ion exchange material refers to the weight (molecular mass) of the polymer in the ionomer divided by the number of sulfonic acid groups. Therefore, a lower equivalent weight indicates a greater acid content. The equivalent weight of an ionomer is referred to in EW if the ionomer has negligible impurities in its proton form at 0% RH. The term “ion exchange capacity” refers to the reciprocal of the equivalent weight (1 / EW).
[0127] As used herein, the “equivalent volume” of an ionomer or ion exchange material refers to the volume of the ionomer divided by the number of sulfonic acid groups. The equivalent volume (EV) of an ionomer refers to the EV if the ionomer is pure at 0% RH and in its proton form (with negligible impurities).
[0128] As used herein, the term "microporous polymer structure" refers to a polymer matrix supporting an ion exchange material, adding structural integrity and durability to the resulting composite membrane. In some exemplary embodiments, the microporous polymer structure comprises expanded polytetrafluoroethylene (ePTFE) having a node and fibril structure. In other exemplary embodiments, the microporous polymer structure comprises a track-etched polycarbonate membrane having a smooth, flat surface, high apparent density, and well-defined pore size.
[0129] As used herein, the internal volume of a microporous polymer structure is referred to as closed or “substantially” closed when the internal volume is characterized by a low vacancy volume (less than 10% by volume) and a Grie number greater than 10,000 s for high gas permeability. Conversely, the internal volume of a microporous polymer structure is referred to as unclosed when the internal volume is characterized by a large vacancy volume (greater than 10% by volume) and a Grie number less than 10,000 s for high gas permeability.
[0130] Composite membrane
[0131] As shown in Figures 1-9, the composite membrane may include multiple (e.g., two or more) reinforcing layers that have been absorbed.
[0132] As shown in Figures 1-4, the provided composite membranes 100, 200, 300, and 400 include two reinforcing layers 105a,b, 205a,b, 305a,b, and 405a,b. Each reinforcing layer comprises a microporous polymer structure and ion exchange materials (e.g., ionomers) 110, 210a,b, 310, and 410 impregnated into the microporous polymer structure of the reinforcing layers 105a,b, 205a,b, 305a,b, and 405a,b. That is, each of the microporous polymer structures of the reinforcing layers 105a,b, 205a,b, 305a,b, and 405a,b absorbs ion exchange materials 110, 210a,b, 310, and 410. Ion exchange materials 110, 210a,b, 310, and 410 can substantially impregnate or seal the microporous polymer structure of reinforcing layers 105a,b, 205a,b, 305a,b, and 405a,b, thereby imparting a substantially closed internal volume (i.e., an internal volume characterized by a low vacancy volume and high gas permeability). For example, by filling more than 90% of the internal volume of the microporous polymer structure of each of the reinforcing layers 105a,b, 205a,b, 305a,b, and 405a,b with ion exchange materials 110, 210a,b, 310, and 410, significant sealing occurs, and the composite membrane is characterized by a Grie number greater than 10,000 s. As shown in Figures 1-4, ion exchange materials 110, 210a,b, 310, and 410 are firmly adhered to the inner and outer surfaces of the microporous polymer structure of the reinforcing layers 105a,b, 205a,b, 305a,b, and 405a,b, forming reinforcing layers 104a,b, 204a,b, 304a,b, and 404a,b that have undergone adsorption.
[0133] In some embodiments, in addition to forming the adsorption-induced reinforcement layers 104a,b, 204a,b, 304a,b, 404a,b in the microporous polymer structure impregnated into the two reinforcement layers 105a,b, 205a,b, 305a,b, the ion exchange materials 110, 210a, 210b, 310, 410 are also provided as one or more additional layers 115a,b, 215a,b, 315a,b, 415a,b on one or more outer surfaces of the adsorption-induced reinforcement layers 104a,b, 204a,b, 304a,b, 404a,b. In other embodiments, ion exchange material 410, 510 is provided only on one of the outer surfaces of the reinforcing layers 404b, 504b where inhalation occurs, and not on the other outer surfaces of the composite membrane (i.e., not on the opposite outer surfaces of the reinforcing layers 404a, 504a where inhalation occurs). Figure 4 and 5In other embodiments, ion exchange material 610 is impregnated only in the microporous polymer structure 605 within the reinforcing layers 604a,b where absorption occurs, i.e., without any additional non-reinforcing ion exchange material layers. Figure 6 However, composite membranes 100, 200, 300, 400, 500, and 600 can be characterized as microporous polymer structures 105a,b, 205a,b, 305a,b, or 405a,b, 500a,b, and 600a,b occupying more than 20% of the total volume of composite membranes 100, 200, 300, 400, 500, 600, 700, 800, and 900. This total volume includes the volume of the reinforcing layer where adsorption occurs and the volume of any additional unreinforced ion exchange material layers 115a,b, 215a,b, 315a,b,c, 415b,c, 515b, 715a,b, and 815a,b,c,d (if present).
[0134] According to Figure 1A and 1B In this embodiment, a first adsorption-induced reinforced layer 104a can be formed by causing the microporous polymer structure of the first reinforced layer 105a to adsorb ion exchange material 110, and a second adsorption-induced reinforced layer 104b can be formed by causing the microporous polymer structure of the second reinforced layer 105b to adsorb the same ion exchange material 110. For example, ion exchange material 110 can be adsorbed into the microporous polymer structure of the first reinforced layer 105a to form the first adsorption-induced reinforced layer 104a, and the same ion exchange material can be adsorbed into the microporous polymer structure of the second reinforced layer 105b to form the second adsorption-induced reinforced layer 104b. In this embodiment, reinforced layers 105a and 105b are in direct contact. In this embodiment, the composite layer has an outer layer of two ion exchange materials 115a and 115b formed on the outer surfaces 114a and 114b of the adsorption-induced reinforced layers 104a and 104b. The layers of ion exchange materials 115a and 115b may contain the same ion exchange material as the reinforcement layers 104a and 104b in which inhalation occurs. Alternatively, one or both layers of ion exchange materials 115a and / or 115b may be different from the reinforcement layers 104a and 104b in which inhalation occurs. The ion exchange materials 115a and 115b in these two layers may be the same or different.
[0135] Although only Figure 1B As shown in the figures, however, in any embodiment of the construction shown in the figures, a composite film 100 may be provided on the backing layer 120. Figure 1BThe backing layer 120 may include a release membrane, such as a cyclic olefin copolymer (COC) layer. In some embodiments, the composite membrane 100 may be peeled off from the backing layer 120 (or otherwise removed from the connection) before being bonded to the membrane electrode assembly (MEA).
[0136] According to Figure 2 In one embodiment, the composite membrane 200 may have a similar structure to the embodiment according to FIG1, having two reinforcing layers 205a and 205b in direct contact with each other. Figure 2 In some embodiments, a first adsorption-induced reinforced layer 204a can be formed by causing the microporous polymer structure of the first reinforced layer 205a to adsorb the first ion exchange material 210a, and a second adsorption-induced reinforced layer 204b can be formed by causing the microporous polymer structure of the second reinforced layer 205b to adsorb the second ion exchange material 210b. In these embodiments, the first ion exchange material 210a can be adsorbed into the microporous polymer structure of the first reinforced layer 205a to form the first adsorption-induced reinforced layer 204a, and the second ion exchange material 210b can be adsorbed into the microporous polymer structure of the second reinforced layer 205b to form the second adsorption-induced reinforced layer 204b. In this embodiment, the composite membrane 200 has an outer layer of two (non-reinforced) ion exchange materials 215a and 215b formed on the outer surfaces 214a and 214b of the adsorption-induced reinforced layers 204a and 204b. The outer layers of ion exchange materials 215a and 215b may contain the same ion exchange material as at least one of the reinforcement layers 204a or 204b in which adsorption occurs. The ion exchange materials of these two outer layers of ion exchange materials 215a and 215b may be the same or different. Alternatively, the ion exchange material of one or both outer layers 215a and / or 215b may be different from the reinforcement layers 204a and 204b in which adsorption occurs. Although not shown in the figures, the composite membrane may have a backing layer or a release layer. The backing layer may be peeled off or removed before the composite membrane is assembled into the electrochemical device.
[0137] According to Figure 3AIn one embodiment, the composite membrane 300 may include two reinforcing layers 305a and 305b that have absorbed ion exchange material 310, thereby forming reinforcing layers 304a,b where absorption has occurred. The composite membrane 300 may include three layers of unreinforced ion exchange material: a first layer 315a formed on the outer surface 314a of the first reinforcing layer 304a where absorption has occurred; a second layer of unreinforced ion exchange material 315b formed on the outer surface 314b of the second reinforcing layer 304b where absorption has occurred; and a third (inner) layer of unreinforced ion exchange material 314b disposed between the reinforcing layers 304a and 304b where absorption has occurred. The ion exchange materials of the unreinforced ion exchange material layers 315a,b,c may be the same or different, and may be the same or different from the ion exchange material 310 of the reinforcing layers 304a and / or 304b where absorption has occurred.
[0138] Figure 3B This illustrates a redox flow cell membrane electrode assembly 350, which includes two electrode layers 320a and 320b sandwiched between the outermost surfaces of a composite membrane 300. Figure 3A The composite membrane 300 is shown. In this specific embodiment, electrode layer 320a is disposed on or attached to the outer surface of unreinforced ion exchange material layer 315a, and electrode layer 320b is disposed on or attached to the outer surface of unreinforced ion exchange material layer 315b. Electrode layers 320a and 320b can be porous layers with a pore size of about 1 to about 200 μm. Electrode layers 320a and 320b can be selected from felt, paper, or woven materials. Electrode layers 320a and 320b may include doped carbon fibers.
[0139] Figure 4 A schematic representative view showing a cross-section of a composite membrane 400 according to another embodiment of this disclosure. The structure is similar to... Figure 3A The membrane 300 has two reinforcing layers 405a, b impregnated with ion exchange material, thereby forming reinforcing layers 304a and 304b that have undergone adsorption. The reinforcing layers 304a, b that have undergone adsorption are separated by an inner layer 415c of unreinforced ion exchange material disposed between the two reinforcing layers 404a and 404b that have undergone adsorption. This composite membrane 400 has a single layer 415b of unreinforced ion exchange material on the outer surface of the reinforcing layer 404b that has undergone adsorption, but no layer of unreinforced ion exchange material on the opposite side (i.e., on the outer surface of the other reinforcing layer 404a that has undergone adsorption).
[0140] Figure 5A schematic representative view showing a cross-section of a composite membrane 500 according to another embodiment of the present disclosure. This structure is similar to the membrane of FIG. 1, having two reinforcing layers 505a, 505b in direct contact with each other, without an intervening unreinforced ion exchange material layer. These two reinforcing layers 505a, b absorb ion exchange material 510 to form reinforcing layers 504a and 504b where absorption occurs. In this example, the composite membrane 500 has a single layer 515b of unreinforced ion exchange material on one outer side of the composite membrane (disposed on the outer surface 514b of the reinforcing layer 504b where absorption occurs), but no layer of unreinforced ion exchange material on the opposite side (i.e., the outer surface 514b of the reinforcing layer 504b where absorption occurs is coated with a layer of unreinforced ion exchange material 515b, but the outer surface 514b of the other reinforcing layer 504a is not coated with a layer of unreinforced ion exchange material).
[0141] According to Figure 6 In some embodiments, the composite membrane 600 may include multiple layers (e.g., two or more layers) of adsorption reinforcing layers 604a and 604b (or more layers, but not shown), which are formed of two (or more) reinforcing layers 605a and 605b comprising a microporous polymer structure, which can adsorb one or more ion exchange materials 610a and 610b (which may be the same or different). Figure 6 In this embodiment, the reinforcing layer where absorption occurs may not have an inner or outer layer of non-reinforcing ion exchange material. That is, the composite membrane 600 may not contain any additional layers of non-reinforcing ion exchange material.
[0142] According to Figure 7In some embodiments, the composite membrane 700 may comprise three reinforcing layers 704a, 704b, and 704c that have undergone adsorption. In these embodiments, the reinforcing layers that have undergone adsorption are in contact with each other (i.e., there is no inner layer of non-reinforcing ion exchange material between the reinforcing layers 704a, 704b, and 704c). Each reinforcing layer that has undergone adsorption may comprise a reinforcing layer 705a, b, or c comprising a microporous polymer structure. The microporous polymer structure of all reinforcing layers 705a, b, or c may be identical. Some of the reinforcing layers 705a, b, or c may have the same microporous polymer structure, while at least one of the reinforcing layers 705a, 705b, or 705c may have a different microporous polymer structure. The microporous polymer structures of reinforcing layers 705a, 705b, and 705c can respectively completely or partially absorb ion exchange materials 710a, 710b, and 710c, imparting a sealing property to the microporous polymer structures and thus forming reinforcing layers 704a, 704b, and 704c, respectively, where absorption has occurred. The ion exchange materials may include one or more ionomers. Each of the ion exchange materials 710a, 710b, and 710c may be identical to or different from all or some of the other ion exchange materials in the composite membrane. Figure 7 The composite membrane 700 shown has a layer 715a of non-reinforced ion exchange material on the outer surface 714a of the first reinforcement layer 704a where adsorption has occurred. The composite membrane has another layer 715b of non-reinforced ion exchange material on the outer surface 714b of the third reinforcement layer 704b where adsorption has occurred (i.e., the outermost reinforcement layer where adsorption has occurred opposite to the reinforcement layer 704a).
[0143] According to Figure 8In this embodiment, the composite membrane 800 may comprise three adsorption-induced reinforcing layers 804a, 804b, and 804c. Each adsorption-induced reinforcing layer may include reinforcing layers 805a, 805b, and 805c comprising microporous polymer structures. The microporous polymer structures of all reinforcing layers 805a, b, and c may be identical. Some of the microporous polymer structures of reinforcing layers 805a, b, and c may be identical, while the microporous polymer structures of at least one of reinforcing layers 805a, 805b, or 805c may be different. The microporous polymer structures of reinforcing layers 805a, 805b, and 805c may respectively completely or partially adsorb ion exchange materials 810a, 810b, and 810c, thereby forming adsorption-induced reinforcing layers 804a, 804b, and 804c, respectively. Ion exchange materials 810a, 810b, and 810c may include one or more ionomers. Each of the ion exchange materials 810a, 810b and 810c may be the same as or different from all or some of the other ion exchange materials in the composite membrane. Figure 8 The composite membrane 800 shown has a layer 815a of unreinforced ion exchange material on the outer surface 814a of the first reinforcement layer 804a where absorption occurs. The composite membrane also has another layer 815b of unreinforced ion exchange material on the outer surface 814b of a third reinforcement layer 804b where absorption occurs. Furthermore, in these embodiments, there is an inner layer 815c of unreinforced ion exchange material located between the reinforcement layers 804a and 804c where absorption occurs. Another inner layer 815d of unreinforced ion exchange material exists between the reinforcement layers 804c and 804b where absorption occurs. The inner layers 815c and 815d form a spacing d between the reinforcement layers 804a and 804c and between the reinforcement layers 804c and 804b where absorption occurs.
[0144] Although not specifically shown, other embodiments of the composite membrane described herein may include three or more layers of adsorption-affected reinforcement layers, each layer comprising a microporous polymer structure and an ion exchange material adsorbed or partially adsorbed into the microporous polymer material. In some embodiments, the composite membrane may have only one outer layer of unreinforced ion exchange material on one outer surface of the composite membrane. In some embodiments, the composite membrane may have outer layers of unreinforced ion exchange material on two outer surfaces of the adsorption-affected layers. In some embodiments, the composite membrane may have one or more inner layers of unreinforced ion exchange material between at least two of the adsorption-affected reinforcement layers. In some embodiments, the composite membrane may have an inner layer of unreinforced ion exchange material between each of the adsorption-affected layers. In some embodiments, the composite membrane may have an inner layer of unreinforced ion exchange material between each of the adsorption-affected reinforcement layers and a single outer layer of unreinforced ion exchange material on one outer surface of the composite membrane. In some embodiments, the composite membrane may have an inner layer of unreinforced ion exchange material between each of the adsorption-affected reinforcement layers and outer layers of unreinforced ion exchange material on both outer surfaces of the composite membrane.
[0145] The adsorption-induced reinforcement layers of composite membranes 100, 200, 300, 400, 500, 600, 700, 800, and 900 can be constructed from reinforcement layers comprising two (or more) different microporous polymer structures. For example, referring to FIG1, a first adsorption-induced reinforcement layer 104a can be formed by causing a first reinforcement layer 105a comprising a first microporous polymer structure to adsorb ion exchange material 110, and a second adsorption-induced reinforcement layer 104b can be formed by causing a second reinforcement layer 105b comprising a second microporous polymer structure to adsorb the same ion exchange material 110. In these embodiments, the first reinforcement layer 105a and the second reinforcement layer 105b are different. The principle of using different types of reinforcement layers in composite membrane construction can be applied to embodiments according to any of the figures. For example, in the case of... Figure 2 In some embodiments, a first reinforced layer 204a that has undergone adsorption can be formed by causing a first reinforcing layer 205a containing a first microporous polymer structure to adsorb a first ion exchange material 210a, and a second reinforced layer 204b that has undergone adsorption can be formed by causing a second reinforced layer 205b containing a second microporous polymer structure to adsorb a second ion exchange material 210b. In these embodiments, the first reinforced layer 205a and the second reinforced layer 205b are different. Therefore, in the composite membrane described herein and shown in the figures, the first microporous polymer structure may be the same as or different from the second microporous polymer structure. The first ion exchange material may be the same as or different from the second ion exchange material.
[0146] In other embodiments, portions of the microporous polymer structures (e.g., top or bottom surface regions) of the reinforcing layers 105a,b, 205a,b, 305a,b, 405a,b, 505a,b, 605a,b, 705a,b,c, and 805a,b,c may include non-enclosed regions (i.e., structures with internal volumes characterized as high cavitation volumes and highly permeable to gases) (not shown in the figures) that contain little or no ion-exchange material. The location of these non-enclosed regions is not limited to the top surface region of the microporous polymer structure. As described above, non-enclosed regions can be provided on the top surface region of any or all of the microporous polymer structures of the reinforcing layers.
[0147] In other embodiments, the unclosed region may contain a small amount of ion-exchange material as thin nodes and filament coatings present on the inner surface of the microporous polymer structure. However, the amount of ion-exchange material cannot be large enough to impart closure to the microporous polymer structure, thus forming the unclosed region.
[0148] Figure 9 Display similar to Figure 6 A schematic representation of the composite membrane 900 shows two reinforcing layers 905a and 905b in direct contact with each other. Each reinforcing layer 905a and 905b comprises a microporous polymer structure. Reinforcing layer 905a has a first surface 911a and a second surface 912a. Similarly, reinforcing layer 905b has a first surface 911b and a second surface 912b. The microporous polymer structure 905b completely absorbs the ion exchange material 910b, forming a closed reinforcing layer 904b where absorption has occurred. However, while the majority of the microporous polymer structure 905a absorbs the ion exchange material 910a, a region 915a, closest to the first surface 911a of the reinforcing layer 905a, contains areas of the microporous polymer structure 905a where absorption has not occurred or where it is not closed. In the context of this disclosure, "majority of absorption" or "significant absorption" can mean that approximately 90% of the microporous polymer structure is closed by the ion exchange material. Therefore, the reinforcing layer 905a forms a partially absorbed reinforcing layer 904a, which is not completely sealed. In other similar embodiments (not shown), the first reinforcing layer 905a includes a region 915a of the non-absorbed or unsealed area of the microporous polymer structure 905a at the second surface 912b closest to the reinforcing layer 905b.
[0149] In similar Figure 9In other embodiments, the first reinforcing layer 905a is completely sealed, but the second reinforcing layer 910b includes a non-absorption or unsealed region of the microporous polymer structure 905a closest to the first surface 911b or the second surface 912b of the reinforcing layer 910b. In other embodiments (not shown), both reinforcing layers 910a and 910b may include a non-absorption or unsealed region at one of the surfaces 911a, 912a, 911b, or 912b of the reinforcing layers 910a and 910b, respectively. The microporous polymer structure of the reinforcing layers 904a and / or 904b where partial aspiration occurs may be approximately 90% sealed by the ion exchange material.
[0150] In embodiments where there is no inner layer of non-reinforced ion exchange material between the at least two reinforcement layers ( Figure 1A , 1B 2, 5, 6, 7 and 9), the at least two reinforcing layers can be in direct contact (i.e., the spacing d between the at least two reinforcing layers is approximately 0 μm).
[0151] In embodiments where the composite membrane comprises an inner layer of unreinforced ion exchange material located between at least two of the reinforcing layers ( Figure 2 (3 and 8), wherein the at least two reinforcing layers may be separated by a spacing d. The spacing d may be: about 1 μm to about 10 μm, or about 2 μm to about 8 μm, or about 4 μm to about 6 μm, or about 1 μm to about 5 μm, or about 5 μm to about 10 μm, or about 6 μm to about 8 μm. The spacing d may also be: about 1 μm, or about 2 μm, or about 3 μm, or about 4 μm, or about 5 μm, or about 6 μm, or about 7 μm, or about 8 μm, or about 9 μm, or about 10 μm. The spacing d may be the thickness of the inner layer of the unreinforced ion exchange material disposed between two adjacent reinforcing layers.
[0152] Microporous polymer structure
[0153] The composite membrane may have at least two reinforcing layers comprising a microporous polymer structure. The composite membrane may have two or more reinforcing layers comprising a microporous polymer structure. For example, the composite membrane may have 2, 3, 4, 5, 6, 7, 8, 9, or 10 reinforcing layers, each containing a microporous polymer structure.
[0154] The suitability of the microporous polymer structure largely depends on the application in which the composite membrane will be used. Preferably, the microporous polymer structure possesses good mechanical properties, is chemically and thermally stable in the environment in which the composite membrane will be used, and is resistant to any additives used in impregnating the ion exchange material.
[0155] As used herein, the term "microporous" refers to a structure having pores. Depending on various optional embodiments, the pores can have an average pore diameter of 0.01 to 100 micrometers, for example, 0.05 to 20 micrometers or 0.1 to 1 micrometer.
[0156] Suitable microporous polymer structures are intended to represent layers with a thickness of at least about 0.1 μm (optionally, about 0.5 μm to about 230 μm, or about 1 μm to about 100 μm, or about 1 μm to about 50 μm) and an average micropore diameter of about 0.05 μm to about 20 μm (e.g., 0.1 μm to 1 μm).
[0157] Suitable microporous polymer structures for reinforcing layers 105a,b, 205a,b, 305a,b, 405a,b, 505a,b, 605a,b, 705a,b,c, 805a,b,c, and 905a,b for electrochemical applications may include porous polymer materials. Porous polymer materials may include: fluoropolymers, chlorinated polymers, hydrocarbons, polyamides, polycarbonates, polyacrylates, polysulfones, copolyether esters, polyethylene, polypropylene, polyvinylidene fluoride, polyaryl ether ketones, polybenzimidazole, poly(ethylene-copoly-tetrafluoroethylene), and poly(tetrafluoroethylene-copoly-hexafluoropropylene). In some embodiments, the microporous polymer structure of the reinforcing layer includes a perfluorinated porous polymer material. Perfluorinated porous polymer materials may include: polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), polyvinylidene fluoride (PVDF), expanded polyvinylidene fluoride (ePVDF), expanded poly(ethylene-co-tetrafluoroethylene) (eEPTFE), or mixtures thereof.
[0158] In some embodiments, the microporous polymer structure includes hydrocarbon materials. Hydrocarbon materials may include polyethylene, expanded polyethylene, polypropylene, expanded polypropylene, polystyrene, polycarbonate, track-etched polycarbonate, or mixtures thereof. Examples of suitable perfluorinated porous polymer materials for fuel cell applications include ePTFE manufactured according to the teachings of U.S. Patent No. 8,757,395 (the entire contents of which are incorporated herein by reference) and various forms commercially available from WLGore & Associates, Inc., Elkton, Maryland.
[0159] In embodiments where the microporous polymer structure includes ePTFE, the total mass of the microporous polymer structure per unit area can be approximately 5.5 g / m². 2 Approximately 20g / m 2 This is based on the total mass per unit area of all microporous layers present in the composite membrane. For example, in embodiments where the microporous polymer structure includes ePTFE, the total mass per unit area of the microporous polymer structure may be approximately 5.5 g / m³.2 Or approximately 5.8g / m 2 or about 6g / m 2 Approximately 7g / m 2 or about 8g / m 2 or about 9g / m 2 or about 10g / m 2 or about 11g / m 2 or about 12g / m 2 or about 13g / m 2 or about 14g / m 2 or about 15g / m 2 or about 16g / m 2 or about 17g / m 2 or about 18g / m 2 or about 19g / m 2 or about 20g / m 2 It is calculated based on the sum of the unit area mass of all microporous layers present in the composite membrane.
[0160] Ion exchange materials
[0161] Suitable ion exchange materials may vary depending on the application in which the composite membrane will be used. Ion exchange materials have an average equivalent volume of approximately 240 cc / mol equivalent to approximately 870 cc / mol equivalent, optionally approximately 240 cc / mol equivalent to approximately 650 cc / mol equivalent, optionally approximately 350 cc / mol equivalent to approximately 475 cc / mol equivalent, and are chemically and thermally stable in the environment in which the composite membrane will be used. Suitable ionomers may include ion exchange materials, such as cation exchange materials, anion exchange materials, or ion exchange materials that simultaneously possess cation and anion exchange capabilities. In some embodiments, the ion exchange material includes a proton-conducting polymer or a cation exchange material. Ion exchange materials may be: perfluorocarboxylic acid polymers, perfluorophosphonic acid polymers, styrene ion exchange polymers, fluorostyrene ion exchange polymers, polyaryletherketone ion exchange polymers, polysulfone ion exchange polymers, bis(fluoroalkylsulfonyl)imides, (fluoroalkylsulfonyl)(fluorosulfonyl)imides, polyvinyl alcohol, polyethylene oxide, divinylbenzene, metal salts containing or not containing polymers, and mixtures thereof. Examples of suitable perfluorosulfonic acid polymers include: (EI DuPont Ltd., Wilmington, Delaware, USA) (Tokyo Asahi Glass Co., Ltd., Japan) (Tokyo Asahi Glass Chemical Co., Ltd., Japan) Solvay Solexis SPA (Italy) and 3M™ (3M Innovative Technologies, USA) are commercially available perfluorosulfonic acid copolymers. Other examples of suitable perfluorosulfonic acid polymers include perfluorinated sulfonyl polymers (polymers), such as those described in U.S. Patent No. 5,463,005.
[0162] Properties of composite membranes
[0163] As discussed above, the composite membrane comprises a microporous polymer structure and an ion-exchange material adsorbed into the microporous polymer structure, thus forming two distinct materials that achieve improved puncture resistance of the composite membrane. Not wishing to be limited by theory, the puncture resistance of the composite membrane may be influenced by the distribution of the total content of the microporous polymer structure in multiple (i.e., at least two) reinforcing layers (compared to the same content of microporous polymer structure provided in a single reinforcing layer in the composite membrane construction). Furthermore, the puncture resistance of the composite membrane may be affected by the total content of the microporous polymer structure within the composite membrane.
[0164] The composite membrane can have a thickness of at least about 10 μm at 0% RH, for example: about 10 μm to about 115 μm, or about 10 μm to about 100 μm, or about 10 μm to about 90 μm, or about 10 μm to about 80 μm, or about 10 μm to about 70 μm, or about 10 μm to about 60 μm, or about 10 μm to about 50 μm, or about 10 μm to about 40 μm, or about 10 μm to about 30 μm, or about 10 μm to about 20 μm, or about 10 μm to about 15 μm, or about 10 μm to about 12 μm, or about 20 μm to about 60 μm, or about 30 μm to about 60 μm, or about 40 μm to about 60 μm, or about 12 μm to about 30 μm, or about 12 μm to about 20 μm, or about 15 μm to about 30 μm, or about 15 μm to about 20 μm, or about 20 μm to about 30 μm. The composite membrane can have the following thicknesses at 0% RH: approximately 10 μm, or approximately 11 μm, or approximately 12, or approximately 13 μm, or approximately 14 μm, or approximately 15 μm, or approximately 16 μm, or approximately 17 μm, or approximately 18 μm, or approximately 19 μm, or approximately 20 μm, or approximately 21 μm, or approximately 22 μm, or approximately 23 μm, or approximately 24 μm, or approximately 25 μm, or approximately 30 μm, or approximately 35 μm, or approximately 40 μm, or approximately 45 μm, or approximately 50 μm, or approximately 55 μm, or approximately 60 μm, or approximately 65 μm, or approximately 70 μm, or approximately 75 μm. The composite membrane can also have a thickness of not less than approximately 10 μm at 0% RH.
[0165] In some embodiments, the microporous polymer structure of the reinforcing layer occupies about 15% to about 70% of the total volume of the composite membrane, or: about 20% to about 70%, or about 30% to about 70%, or about 40% to about 70%, or about 50% to about 70%, or about 65% to about 70%, or about 25% to about 60%, or about 20% to about 50%, or about 20% to about 40%, or about 20% to about 30%, or about 40% to about 60%, or about 40% to about 50% of the total volume of the composite membrane. The amount of the microporous polymer structure present in the reinforcing layer can be: about 15% by volume, or about 20% by volume, or about 25% by volume, or about 30% by volume, or about 35% by volume, or about 40% by volume, or about 45% by volume, or about 50% by volume, or about 55% by volume, or about 60% by volume, or about 65% by volume, or about 70% by volume, based on the total volume of the composite membrane.
[0166] In some embodiments, the equivalent volume of the ion exchange material 110 is from about 240 cc / mol equivalent to about 870 cc / mol equivalent. The ion exchange material may have an SO3 content of from about 400 g / equivalent to about 2000 g / equivalent. - The total equivalent weight (EW). In various embodiments, at 0% relative humidity, the acid content of the composite membranes 100, 200, 300, 400, 500, 600, 700, 800, and 900 is greater than 1.2 meq / cc, for example, from 1.2 meq / cc to 3.5 meq / cc. In various embodiments, the thickness of the composite membrane is from about 10 μm to about 115 μm. Specifically, according to embodiments, the thickness of the composite membrane is from about 10 μm to about 115 μm while the acid content of the composite membrane is maintained at 1.2 meq / cc to 3.5 meq / cc.
[0167] The volume percentage (%) of the microporous polymer structure in the reinforcing layer of a composite material refers to the space occupied by the microporous polymer structure, which does not contain ionomers. Therefore, the volume percentage of the microporous polymer structure in the composite material differs from that of a layer containing ionomers that has undergone adsorption. The volume percentage of the microporous polymer structure in the composite material is affected by humidity. Therefore, the experiments regarding volume percentage discussed below were conducted under dry conditions (e.g., 0% relative humidity (RH)).
[0168] In some embodiments, the normalized total content of the microporous polymer structure within the composite membrane can be at least about 3.10. -6 m, or approximately 3.5 × 10⁻⁶ m. -6 m, or about 4.10 -6 m, or approximately 4.5 × 10⁻⁶ m. -6m, or about 5.10 -6 m, or approximately 5.5 × 10⁻⁶ m. -6 m, or approximately 6.10 -6 m, or approximately 6.5 × 10 -6 m, or about 7.10 -6 m, or about 8.10 -6 m, or approximately 8.5 × 10 -6 m, or approximately 9.10 -6 m, based on the total area of the composite membrane.
[0169] The equivalent weight of ion exchange materials is also affected by humidity. Therefore, the experiments on equivalent weight discussed below were conducted under ideal conditions of dryness (e.g., 0% relative humidity (RH)), where the presence of water does not affect the numerical value of the equivalent volume and allows for meaningful comparisons between different ionomers.
[0170] As provided above, surprisingly and unexpectedly, for any given content of microporous polymer structure and composite membrane thickness, the puncture resistance of the composite membrane is dramatically improved by distributing the content of microporous polymer structure in two or more reinforcing layers.
[0171] When measured by the mean puncture pressure failure test described below, the composite membrane may have a mean failure pressure of at least about 150 psi. For example, when measured by the mean puncture pressure failure test described below, the composite membrane may have a mean failure pressure of at least about 150 psi, or at least about 160 psi, or at least about 170 psi, or at least about 180 psi, or at least about 190 psi, or at least about 200 psi.
[0172] When measured by the mean puncture pressure failure test described below, the composite membrane may have a mean failure pressure of about 150 psi to about 500 psi, or when measured by the mean puncture pressure failure test described below, the composite membrane may have a mean failure pressure of about 150 psi to about 450 psi, or about 150 psi to about 400 psi, or about 150 psi to about 350 psi, or about 150 psi to about 300 psi, or about 200 psi to about 400 psi, or about 200 psi to about 350 psi.
[0173] When measured by the mean puncture pressure failure test described below, the composite membrane may have the following mean failure pressures: approximately 150 psi, or approximately 200 psi, or approximately 250 psi, or approximately 300 psi, or approximately 350 psi, or approximately 400 psi, or approximately 450 psi, or approximately 500 psi.
[0174] According to, for example, Figure 13 The membrane is prepared using the sequential coating process shown. For membranes with ionomer inner layers between reinforcing layers, method 1500 ( Figure 13 This includes the following steps:
[0175] 1510) The backing is coated with the first ionomer solution in the following manner: a backing layer and a liquid layer for depositing the first ionomer solution are provided;
[0176] 1520) A first reinforcing layer comprising a microporous polymer structure is stacked (deposited) over the liquid layer of the first ionomer solution, and the microporous polymer structure of the first reinforcing layer is such that it absorbs or at least partially absorbs the first ionomer solution.
[0177] 1530) Optionally, the laminate is dried;
[0178] 1540) The first reinforcing layer that was absorbed was coated with a liquid layer of the second ionomer solution;
[0179] 1550) A second reinforcing layer comprising a microporous polymer structure is stacked (deposited) over the liquid layer of the second ionomer solution, such that the microporous polymer structure of the second reinforcing layer absorbs or at least partially absorbs the second ionomer solution.
[0180] 1560) Optionally, the laminate is dried;
[0181] 1570) Coat the outermost surface of the laminate furthest from the backing with the final liquid layer of the third ionomer solution; and
[0182] 1580) Dry the laminate.
[0183] Optionally, the manufacturing method includes repeating steps 1560), 1570), and 1580) with other reinforcing layers and a liquid layer of ionomer solution, and drying the laminate. For example, for a composite membrane comprising three reinforcing layers, a third liquid layer of a third ionomer solution may be deposited over a second reinforcing layer where absorption occurs, and a third reinforcing layer may be applied over the third layer of ionomer solution, and then the laminate may be dried. In some embodiments, the process includes adding even more ionomers and reinforcing layers, and drying the laminate.
[0184] Membrane electrode assemblies can be prepared by depositing electrodes (i.e., anode and cathode) on a composite membrane using any suitable technique known in the art. For example, a solid electrode layer can be laminated against the composite membrane using any suitable technique. Alternatively, (liquid) electrode ink can be applied to the composite membrane. After the composite dries, the solvent in the electrode ink can be dried to form a solid electrode layer. To avoid ambiguity, the backing must be removed from the composite membrane before applying the cathode or cathode fluid diffusion layer. The ionomers in the ionomer solutions used in each ionomer layer can be the same or different. The reinforcing layers used in the electrolyte composite membrane can all be the same, or at least one of the reinforcing layers can be different.
[0185] Example
[0186] Test procedures and measurement schemes used in the embodiments
[0187] Bubble
[0188] Bubble point is measured according to the procedure in ASTM F316-86. Isopropanol is used as the wetting liquid to fill the pores of the test specimen. The bubble point is the air pressure required to generate the first detectable continuous flow of bubbles that rise through the isopropanol layer covering the microporous polymer matrix. This measurement provides an assessment of the maximum pore size.
[0189] Non-contact thickness
[0190] The microporous polymer structure sample was placed on a flat, smooth metal anvil and taut to remove wrinkles. The height of the microporous polymer structure was measured and recorded using a non-contact Keyence LS-7010M digital micrometer. The anvil height without the microporous polymer matrix was then recorded. The thickness of the microporous polymer structure was taken as the difference between the micrometer readings with and without the microporous structure on the anvil.
[0191] Mass per unit area
[0192] Each microporous polymer structure is fully stretched to eliminate wrinkles, and then cut into 10cm sections using a die. 2 Sheet material. 10cm 2 The sheet material was weighed on a standard laboratory balance. The ratio of the measured mass to the known area was then calculated as the mass per unit area (M / A). This process was repeated twice, and the average value of M / A was calculated.
[0193] Apparent density of microporous polymer structures
[0194] The apparent density of the microporous polymer structure was calculated using non-contact thickness and mass per unit area data, and the following equation was used:
[0195]
[0196] Porosity of microporous polymer structures
[0197] The porosity of the microporous polymer structure was calculated using the following equation based on apparent density and framework density data:
[0198]
[0199] Solid concentration of ion exchange material (IEM) solution
[0200] Here, the terms "solution" and "dispersion" are used interchangeably when referring to ion exchange materials (IEMs). This testing procedure applies to solutions in which the IEM is in proton form and contains negligible amounts of other solids. A 2 cubic centimeter volume of IEM solution is drawn into a syringe, and the mass of the syringe containing the solution is measured using a balance in a solids analyzer (purchased from CEM Corporation, USA). The masses of two sheets of glass fiber paper (purchased from CEM Corporation, USA) are also measured and recorded. The IEM solution is then deposited from the syringe into these two layers of glass fiber paper. The glass fiber paper containing the ionomer solution is placed in the solids analyzer and heated to 160°C to remove the solvent liquid. Once the masses of the glass fiber paper and the residual solids cease to change with increasing temperature and time, they are recorded. It is assumed that the residual IEM does not contain water (i.e., the mass of the ionomer corresponding to 0% RH). The mass of the empty syringe is then measured and recorded using the same balance as before. The ionomer solids in the solution are calculated according to the following equation:
[0201]
[0202] Equivalent weight (EW) of IEM
[0203] The following testing procedure applies to IEMs containing single ionomer resins or mixtures of ionomer resins in proton form (i.e., containing negligible amounts of other cations) and containing negligible amounts of other substances (including protic acids and dissociated salts). If these conditions are not met, the solution must be purified of the ionic impurities according to a suitable procedure known to those skilled in the art before testing, or the impurities must be characterized and their effects on the EW test results must be corrected.
[0204] As used herein, the EW of an IEM refers to the state of the IEM in its proton form at 0% RH with negligible impurities. An IEM may include a single ionomer or a mixture of ionomers in proton form. Pour the volume of the IEM solution containing 0.2 g of solids, as determined above, into a plastic cup. Measure the mass of the ionomer solution using a standard laboratory balance (Mettler Toledo, Inc., USA). Then, add 5 mL of deionized water and 5 mL of 200 mL of proof denatured ethanol (SDA 3C, Sigma-Aldrich, Inc., USA) to the ionomer solution in the cup. Then, add 55 mL of 2N sodium chloride solution in water to the IEM solution. The sample is then equilibrated with constant stirring for 15 minutes. After equilibration, the sample is titrated with 1N sodium hydroxide solution. Record the volume of 1N sodium hydroxide solution required to neutralize the sample solution to pH 7. The EW of an IEM (EW) IEM The calculation is as follows:
[0205]
[0206] When multiple IEMs are combined to manufacture a composite membrane, the average EW of the IEMs in the composite membrane is calculated using the following equation:
[0207]
[0208] In the formula, the mass fraction of each IEM is relative to the total content of all IEMs. This equation applies to both composite membranes containing ionomer blends and composite membranes containing ionomer layers.
[0209] Equivalent volume (EV) of ion exchange materials
[0210] As used herein, the equivalent volume of an IEM refers to the EV if the IEM is pure at 0% RH and in its proton form (with negligible impurities). The EV is calculated according to the following equation:
[0211]
[0212] The equivalent weight of each IEM is determined according to the procedure described above. The IEM used in these applications is the perfluorosulfonic acid ionomer value, with a bulk density of 1.9 g / cc at 0% RH for the perfluorosulfonic acid ionomer resin.
[0213] Thickness of composite membrane
[0214] Before measurement, allow the composite film to equilibrate in the room where the thickness measurement will be performed for at least 1 hour. Attach the composite film to the substrate on which it is coated. For each sample, place the composite film on its coated substrate on a smooth, flat, horizontal marble slab. A thickness gauge (purchased from Heidenhain, USA) is in contact with the composite film, and height readings are recorded at six different points on the film arranged in a grid pattern. The sample is then removed from the substrate, the gauge is in contact with the substrate, and height readings are recorded again at the same six points. The difference between the height readings of the gauge with and without the composite film is calculated as the thickness of the composite film at a given relative humidity (RH) in the room. Local RH is measured using an RH probe (purchased from Fluke). The thickness at 0% RH is calculated using the following general equation:
[0215]
[0216] In the formula, the parameter λ corresponds to the water uptake of the ion exchange material at a specific RH, and the unit is moles of water / moles of acid groups. For PFSA ionomers, the value of λ at any RH range of 0 to 100% in the gas phase is calculated according to the following equation:
[0217] λ = 80.239 × RH 6 -38.717×RH 5 -164.451×RH 4 +208.509×RH 3 -91.052×RH 2 +21.740×RH 1 +0.084
[0218] Microporous polymer matrix (MPM) volume content of composite membrane
[0219] Calculate the volume percentage of the microporous polymer matrix in each composite membrane using the following equation:
[0220]
[0221] The microporous polymer matrices used in these embodiments are ePTFE and track-etched porous polycarbonate. The matrix skeleton density of ePTFE is 2.25 g / cc, and the matrix skeleton density of track-etched porous polycarbonate is 1.20 g / cc.
[0222] Acid content of composite membrane
[0223] The acid content of the composite membrane can be calculated using the following equation:
[0224]
[0225] Sphere burst test of composite microporous layer
[0226] The mechanical strength of the composite membrane prepared according to the present invention is measured by subjecting the sample to load pressure.
[0227] The sample was taut and secured in a frame with a 45mm diameter opening. The sample was then placed in the Shimadzu AG-I universal testing machine, an environmentally controlled chamber with an indoor temperature and relative humidity of 23°C and 80%, respectively. A 6.35mm diameter steel ball, supported on a rod, was pressed into the suspended membrane at a constant rate of 100mm / min. The maximum load generated by the system when the sample burst was recorded and this value was termed the ball burst strength.
[0228] Mean puncture pressure failure test
[0229] The sample was placed between two porous carbon electrodes (Sigracet 39AA carbon paper) and mounted on an Instron Model 5542, a 14mm diameter gold-plated cylindrical plate with electrical isolation. The sample and electrode areas were larger than the plate and extended beyond it to eliminate edge effects during puncture. The sample area was also larger than the electrode area to prevent electrode contact and the creation of electrical short circuits that would not penetrate the sample. The resistance on the membrane was measured using a Keithley 580 microohmmeter connected to the top and bottom plates. The top plate was lowered at a rate of 1mm / min under ambient conditions while applying a compressive mechanical load to the sample, and the resistance measured on the sample was continuously recorded until 444.8 N (100 lbf) was applied; higher compressive pressures could be obtained using alternative instruments or smaller plate activity areas. Membrane puncture was defined as the pressure at which the resistance dropped below 18,000 ohms, representing physical contact between the electrode or electrode fiber and the sample. Each sample was tested five times, and the average of the five tests was recorded as the mean puncture pressure. The puncture pressure depends on the electrode material and may increase or decrease significantly if an alternative electrode material is used.
[0230]
[0231] Example
[0232] The composite membrane of this disclosure can be better understood by referring to the following non-limiting embodiments.
[0233] To determine properties such as the acid content, volume, and puncture resistance of the composite membrane, as well as the nature of the testing process, measurement protocols were employed as described above. Table 1 shows the properties of the composite membranes according to embodiments of the present invention and comparative examples. Table 2 shows the properties of the microporous polymer structures used in various testing processes in five series of embodiments according to some aspects of the present invention and comparative examples.
[0234] Ion exchange materials manufactured according to aspects of this disclosure in all embodiments
[0235] All ion exchange materials used in the following examples were ionomers based on perfluorosulfonic acid (PFSA) with equivalent weights (EW) as specified in Table 1. Prior to fabrication of the composite membrane, all ionomers were in solution form using water and ethanol as solvents, with the water content in the solvent phase being less than 50%.
[0236] The composite membranes of this disclosure are produced using well-known ion exchange materials. A preferred example is a solution obtained by dispersing or dissolving a solid PFSA ionomer represented by the following general formula (where a:b = 1:1 to 9:1 and n = 0, 1 or 2) in a solvent.
[0237]
[0238] In some respects, the solvent is selected from the group consisting of: water; alcohols, such as methanol, ethanol, propanol, n-butanol, isobutanol, sec-butanol and tert-butanol; pentanol and its isomers; hexanol and its isomers; hydrocarbon solvents, such as n-hexane; ether solvents, such as tetrahydrofuran and dioxane; sulfoxide solvents, such as dimethyl sulfoxide and diethyl sulfoxide; formamide solvents, such as N,N-dimethylformamide and N,N-diethylformamide; acetamide solvents, such as N,N-dimethylacetamide and N,N-diethylacetamide; pyrrolidone solvents, such as N-methyl-2-pyrrolidone and N-vinyl-2-pyrrolidone; 1,1,2,2-tetrachloroethane; 1,1,1,2-tetrachloroethane; 1,1,1-trichloroethane; 1,2-dichloroethane; trichloroethylene; tetrachloroethylene; dichloromethane; and chloroform. In this disclosure, the solvent is optionally selected from the group consisting of water, methanol, ethanol, and propanol. Water and the above solvents may be used alone or in combination of two or more.
[0239] Series 1
[0240] Prior art embodiment 1
[0241] Example 1 of the prior art was prepared according to the following process: ePTFE membrane 1 (with a unit area mass of 2.8 g / m³) was prepared. 2 A microporous polymer structure with a thickness of 9.6 μm, an apparent density of 0.29 g / cc, and a bubble point of 34.4 psi was used as the reinforcing layer. PSFA solution was used as the IEM (EW = 810 g / mol equivalent SO3). -(Purchased from Gore 3F Fluorine Materials Co., Ltd., Shanghai, China; solution composition: 17.3% water, 71.5% ethanol, 11.2% solids) was applied to the top side of the backing layer using a drop strip as the first deposit, with a theoretical wettable coating thickness of 3 mils (76.2 μm). While the coating was still wet, a first reinforcing layer of the ePTFE membrane 1, previously confined to the metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. On the second deposit, the same IEM solution was applied to the top surface of the first ePTFE membrane 1 using a drop strip, with a theoretical wettable coating thickness of 4 mils (101.6 μm). While the coating was still wet, a second reinforcing layer of the ePTFE membrane 1, previously confined to the metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. On the third sediment, PSFA solution was used as an IEM (EW = 810 g / mol equivalent SO3). - (Purchased from Gore 3F Fluorine Materials Co., Ltd., Shanghai, China; solution composition: 6.2% water, 89.8% ethanol, 4.0% solids) was applied to the top surface of the second reinforcing layer using a drop strip, with a theoretical wettable coating thickness of 3 mils (76.2 μm). The composite membrane was then dried again at 165°C. The multilayer composite membrane is completely closed and has an IEM layer on each side and between the two completely closed microporous polymer layers. The resulting composite membrane has a thickness of 8.66 μm at 0% RH.
[0242] Comparative Example 1.1
[0243] Comparative Example 1.1 was manufactured according to the following process: ePTFE membrane 2 (mass per unit area of 6 g / m²) 2 The material (19.7 μm thick, with an apparent density of 0.29 g / cc and a bubble point of 34.8 psi) was manually stretched to eliminate wrinkles and then confined in this state using a metal frame. Next, a PSFA solution (EW = 810 g / mol equivalent SO3) was applied. -The first deposit of an IEM (purchasing from Asahi Glass Co., Ltd.), with a solution composition of 32.2% water, 49.6% ethanol, and 18.2% solids, was coated onto the top side of a polymer substrate (backing material). The polymer substrate (purchasing from Daicel Value Coating Ltd., Japan) contained a protective layer of PET and a cyclic olefin copolymer (COC), oriented such that the COC side was on top. IEM (PFSA solution) coating was performed using a Meyer bar, with a theoretical wetted coating thickness of 3 mils (76.2 μm). While the coating was still wet, two layers of an ePTFE membrane previously confined to a metal frame were stacked onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure (ePTFE membrane) became completely absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer substrate. On the second deposit, an IEM solution with the same EW and a composition of 18.4% water, 73.3% ethanol, and 8.3% solids was applied using a drop bar to the top surface of the ePTFE membrane 2 (the surface opposite the polymer substrate), with a theoretical wettable coating thickness of 2.5 mils (63.5 μm). The composite membrane was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer structure. The composite membrane was completely closed and had an IEM layer on each side of the microporous polymer structure. The resulting composite membrane had a thickness of 8.6 μm at 0% RH.
[0244] Comparative Example 1.2
[0245] Comparative Example 1.2 was prepared according to the same process as described in Comparative Example 1.1, except that different materials were used. The ePTFE membrane 3 (with a unit area mass of 3.9 g / m³) was used. 2 A microporous polymer structure with a thickness of 11.7 μm, an apparent density of 0.34 g / cc, and a bubble point of 97.5 psi was used. PSFA solution was used as the IEM (EW = 710 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition was 26.4% water, 61.6% ethanol, and 12% solids) and applied using a drop bar to the top side of a polymer substrate (backing material) as the first deposit, with a theoretical wetting coating thickness of 4 mils (101.6 μm). While the coating was still wet, an ePTFE membrane 3, previously confined to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure (ePTFE membrane) became fully absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer substrate. On the second deposit, the same IEM solution with a composition of 41% water, 53% ethanol, and 6% solids was applied using a drop bar to the top surface of the ePTFE membrane 3 (the surface opposite the polymer substrate), with a theoretical wetting coating thickness of 2 mils (50.8 μm). The composite material was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer structure. The composite membrane was completely sealed and had an IEM layer on each side of the microporous polymer substrate. The resulting composite membrane had a thickness of 7.8 μm at 0% RH.
[0246] Series 2
[0247] Prior art embodiment 2
[0248] Example 2 of the prior art was prepared according to the following process: First, two microporous polymer structures (first ePTFE membrane 4 (unit area mass of 3.1 g / m²)) were prepared. 2 The first ePTFE membrane has a thickness of 13.3 μm, an apparent density of 0.33 g / cc, and a bubble point of 55.5 psi, while the second ePTFE membrane has a mass per unit area of 3.0 g / m³. 2 (15.2 μm thick, apparent density 0.20 g / cc, and bubble point 36.6 psi) Tightened to eliminate wrinkles, and confined one to the top of the other touching the metal frame. Next, an IEM solution (EW = 810 g / mol equivalent SO3) was applied. -The first deposit (purchased from Gore 3F Fluorine Materials Co., Ltd., Shanghai, China) with a solution composition of 17.3% water, 71.5% ethanol, and 11.2% solids) was coated onto the top side of a polymer substrate (backing material). The polymer substrate (purchased from Daicel Value Coating Ltd., Japan) contained a protective layer of PET and a cyclic olefin copolymer (COC), oriented such that the COC side was on top. The first deposit was applied using a drop strip, with a theoretical wettable coating thickness of 5 mils (127 μm). While the coating was still wet, ePTFE membranes 4 and 6, previously confined to a metal frame, were laminated onto the coating. Following this, the IEM solution was drawn into the pores of the microporous polymer structure. The multilayer composite was then dried in a convection oven at 165°C with air. After drying, the microporous polymer matrix was fully infused with the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer matrix and the polymer substrate. On the second sediment, the IEM solution (EW = 810 g / mol equivalent SO3) - (Purchased from Gore 0.5F Fluorine Materials Co., Ltd., Shanghai, China; solution composition: 4% water, 95.0% ethanol, 1% solids) was applied to the top surface of the composite material (the surface opposite the polymer substrate) using a drop coat, with a theoretical wettable coating thickness of 0.5 mils (12.7 μm). The multilayer composite material was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer matrix. The multilayer composite material comprises a multilayer composite film bonded to the substrate. The multilayer composite film is completely closed and has an IEM layer on each side of the contacting microporous polymer structure. The resulting multilayer composite film has a thickness of 7.1 μm at 0% RH.
[0249] Comparative Example 2.1
[0250] Comparative Example 2.1 was prepared according to the same process as described in Comparative Example 1.1, except that different materials were used. An ePTFE membrane 5 (with a unit area mass of 4.5 g / m³) was used. 2 A 23 μm thick, 0.2 g / cc apparent density, and 55.8 psi bubble point were used as the microporous polymer structure. PSFA solution was used as the IEM (EW = 810 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition was 33% water, 48.8% ethanol, and 18.2% solids) was applied to the top side of the polymer substrate (backing material) using a drop strip as the first deposit, with a theoretical wetting coating thickness of 3 mils (76.2 μm). While the coating was still wet, an ePTFE membrane 5, previously confined to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure (ePTFE membrane 5) became fully absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer substrate. On the second deposit, the same IEM solution with a composition of 35% water, 56.7% ethanol, and 8.3% solids was applied to the top surface of membrane 5 (the surface opposite the polymer substrate) using a drop strip, with a theoretical wetting coating thickness of 3 mils (76.2 μm). The composite material was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer structure. The composite membrane was completely sealed and had an IEM layer on each side of the microporous polymer substrate. The resulting composite membrane had a thickness of 8.8 μm at 0% RH.
[0251] Series 3
[0252] Comparative Example 3.1
[0253] Comparative Example 3.1 was prepared according to the same process as described in Comparative Example 1.1, except that different materials were used. An ePTFE membrane 7 (with a unit area mass of 10.4 g / m³) was used. 2 A layer with a thickness of 62.2 μm, an apparent density of 0.16 g / cc, and a bubble point of 56.2 psi was used as a microporous polymer structure. PSFA solution was used as an IEM (EW = 710 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition was 32% water, 49.8% ethanol, and 18.2% solids) was applied using a drop bar to the top side of the polymer substrate (backing material) on the first deposit, with a theoretical wetting coating thickness of 9 mils (228.6 μm). While the coating was still wet, an ePTFE membrane 7, previously confined to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure (ePTFE membrane 7) became fully absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer substrate. On the second deposit, the same IEM solution, with a composition of 41% water, 53% ethanol, and 6% solids, was applied using a drop bar to the top surface of the ePTFE membrane 7 (the surface opposite the polymer substrate), with a theoretical wetting coating thickness of 3 mils (76.2 μm). The composite material was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer structure. The composite membrane was completely sealed and had an IEM layer on each side of the microporous polymer substrate. The resulting composite membrane had a thickness of 15.3 μm at 0% RH.
[0254] Embodiment 3.2 of the present invention
[0255] Example 3.2 of the present invention was prepared according to the following process: The first ePTFE membrane 3 (with a unit area mass of 3.9 g / m³) was prepared. 2 A microporous polymer structure with a thickness of 11.7 μm, an apparent density of 0.34 g / cc, and a bubble point of 97.5 psi was used as the reinforcing layer. PSFA solution was used as the IEM (EW = 710 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition is 35% water, 55.1% ethanol, and 9.9% solids). A first deposit (ePTFE membrane 3, previously confined to a metal frame, was applied to the top side of a polymer substrate (backing layer) using a drop bar, with a theoretical wetting coating thickness of 5 mils (127 μm). While the coating was still wet, a first ePTFE membrane 3, confined to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure (ePTFE membrane 3) became fully absorbed by the IEM. A second deposit (the surface opposite the polymer substrate) of the same IEM solution was applied to the top surface of the first membrane 3 using a drop bar, with a theoretical wetting coating thickness of 5 mils (127 μm). While the coating was still wet, a second ePTFE membrane 3, previously confined to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. A third deposit (solution composition: 38.0% water, 57.7% ethanol, 4.3% solids) of a PSFA solution with the same IEM EW was applied to the top surface of the second membrane 3 using a drop strip, with a theoretical wetted coating thickness of 3 mils (76.2 μm). This composite material was then dried in a convection oven at 165°C with air. The multilayer composite membrane is completely closed and has an IEM layer on each side and between the two completely closed microporous polymer layers of membrane 3 spaced at a distance d of approximately 2 μm. The resulting composite membrane has a thickness of 14.5 μm at 0% RH.
[0256] Embodiment 3.3 of the present invention
[0257] Example 3.3 of the present invention was prepared according to the following process: ePTFE membrane 5 (with a unit area mass of 4.5 g / m³) was prepared. 2 A microporous polymer structure with a thickness of 23 μm, an apparent density of 0.20 g / cc, and a bubble point of 55.8 psi was used as the reinforcing layer. PSFA solution was used as the IEM (EW = 710 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition is 33% water, 52.2% ethanol, and 14.8% solids). A first deposit (3 mils, 76.2 μm) was applied to the top side of a polymer substrate (backing layer) using a drop bar, with a theoretical wetting coating thickness of 3 mils. While the coating was still wet, a first ePTFE membrane 5, constrained to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure (ePTFE membrane) became fully absorbed by the IEM. A second deposit (the surface opposite the polymer substrate) of the same IEM solution was applied to the top surface of the first membrane 5 composite material (using a drop bar), with a theoretical wetting coating thickness of 6 mils (152.4 μm). While the coating was still wet, a second ePTFE membrane 5, previously constrained to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. A third deposit (solution composition: 10.0% water, 89.0% ethanol, 1.0% solids) of a PSFA solution with the same IEM and EW was applied to the top surface of the second membrane 5 using a drop strip, with a theoretical wetted coating thickness of 1.5 mils (38.1 μm). This composite material was then dried in a convection oven at 165°C with air. The multilayer composite membrane is completely closed and has an IEM layer on each side and between the two completely closed microporous polymer layers of membrane 5 spaced at a distance d of approximately 2 μm. The resulting composite membrane has a thickness of 14.4 μm at 0% RH.
[0258] Series 4
[0259] Comparative Example 4.1
[0260] Comparative Example 4.1 was prepared according to the same process as described in Comparative Example 1.1, except that different materials were used. The ePTFE membrane 7 (with a unit area mass of 10.4 g / m³) was used. 2 A layer with a thickness of 62.2 μm, an apparent density of 0.16 g / cc, and a bubble point of 56.2 psi was used as a microporous polymer structure. PSFA solution was used as an IEM (EW = 710 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition was 32% water, 49.8% ethanol, and 18.2% solids). The solution was applied using a drop-down coating onto the top side of the polymer substrate (backing material) on the first deposit, with a theoretical wetting coating thickness of 9 mils (228.6 μm). The membrane was then dried in a convection oven at 165°C with air present. On the second deposit, the same IEM solution with a composition of 41% water, 53% ethanol, and 6% solids was applied using a drop-down coating onto the top surface of membrane 7, with a theoretical wetting coating thickness of 3 mils (76.2 μm). The membrane was again dried in a convection oven at 165°C with air present. The composite membrane is completely sealed and has an IEM layer on each side of the microporous polymer substrate. The resulting composite membrane has a thickness of 15.3 μm at 0% RH.
[0261] Embodiment 4.2 of the present invention
[0262] Example 4.2 of the present invention was prepared according to the following process: First, two microporous polymer structures of ePTFE membranes 5 were used as reinforcing layers (mass per unit area of 4.5 g / m²). 2 (The thickness is 23 μm, the apparent density is 0.20 g / cc, and the bubble point is 55.8 psi) Tightening is used to eliminate wrinkles, and one is confined to the top of the other touching the metal frame. Next, an IEM solution (EW = 710 g / mol equivalent SO3) is applied. - The first deposit (purchased from Asahi Glass Co., Ltd., with a solution composition of 33% water, 52.2% ethanol, and 14.8% solids) was coated onto the top side of the polymer substrate (backing layer). The polymer substrate (purchased from Daicel Value Coating Ltd., Japan) contained a protective layer of PET and a cyclic olefin copolymer (COC), oriented such that the COC side was on top. Coating was performed using a drop strip, with a theoretical wetted coating thickness of 7 mils (177.8 μm). While the coating was still wet, two ePTFE membranes previously confined to a metal frame were stacked in five layers onto the coating, after which the IEM solution was drawn into the pores. This multilayer composite was then dried in a convection oven at 165°C with air. After drying, the microporous polymer matrix became completely absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer structure and the polymer substrate. On the second deposit, the IEM solution (EW = 710 g / mol equivalent SO3) was applied. -(Purchased from Asahi Glass Co., Ltd., the solution composition was 33% water, 52.2% ethanol, and 14.8% solids). The ePTFE membrane 5 was coated using a drop strip onto the top surface (the surface opposite the polymer substrate), with a theoretical wettable coating thickness of 1.5 mils (38.1 μm). The multilayer composite was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer matrix. The multilayer composite membrane was completely sealed and had an IEM layer on each side of the contacting microporous polymer matrix. The resulting multilayer composite membrane had a thickness of 14.4 μm at 0% RH.
[0263] Embodiment 4.3 of the present invention
[0264] Example 4.3 of the present invention was prepared according to the same process as described above in Example 3.3 of the present invention.
[0265] Embodiment 4.4 of the present invention
[0266] Example 4.4 of the present invention was prepared according to the same process as described in Example 3.3 of the present invention, except that different materials were used. The ePTFE membrane 5 (with a unit area mass of 4.5 g / m³) was used. 2 A microporous polymer structure with a thickness of 23 μm, an apparent density of 0.20 g / cc, and a bubble point of 55.8 psi was used as the reinforcing layer. PSFA solution was used as the IEM (EW = 710 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd.), the solution composition was 29.8% water, 56.8% ethanol, and 13.4% solids. It was applied as the first deposit using a drop-down coating onto the top side of a polymer substrate (backing layer), with a theoretical wetting coating thickness of 4 mils (101.6 μm). While the coating was still wet, a first ePTFE membrane 5, previously confined to a metal frame, was laminated onto the coating. After this, the IEM solution was drawn into the pores. The composite material was then dried in a convection oven at 165°C with air. After drying, the microporous polymer structure became fully absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer structure and the polymer substrate. On the second deposit, the same IEM solution with a composition of 29.8% water, 56.8% ethanol, and 13.4% solids was applied as the top surface of the first ePTFE membrane 5 using a drop-down coating, with a theoretical wetting coating thickness of 5 mils (127 μm). Five layers of the second ePTFE membrane, previously confined to a metal frame, were stacked onto the coating layer. Following this, an IEM solution was drawn into the pores. This multilayer composite was then dried in a convection oven at 165°C with air. On the third deposit, the same IEM solution with a composition of 35% water, 59% ethanol, and 6% solids was applied using a drop coat, with a theoretical wetted coating thickness of 2 mils (50.8 μm). This composite was then dried in a convection oven at 165°C with air. The multilayer composite membrane is completely closed and contains an IEM layer on each side and between two completely closed microporous polymer layers spaced approximately 4 μm apart. The resulting composite membrane has a thickness of 14.4 μm at 0% RH.
[0267] Series 5
[0268] Comparative Example 5.1
[0269] Comparative Example 5.1 was prepared according to the same process as described in Comparative Example 1.1, except that different materials were used. An ePTFE membrane 8 (with a unit area mass of 18 g / m³) was used. 2 A layer with a thickness of 33.4 μm, an apparent density of 0.53 g / cc, and a bubble point of 23.7 psi was used as a microporous polymer structure. PSFA solution was used as an IEM (EW = 810 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd.), the solution composition was 32.2% water, 49.6% ethanol, and 18.2% solids. A drop-coating method was used as the first deposit, with a theoretical wetting coating thickness of 9 mils (228.6 μm). While the coating was still wet, the first ePTFE membrane 8, previously confined to a metal frame, was laminated onto the coating. Afterward, the IEM solution was drawn into the pores. This composite material was then dried in a convection oven at 165°C with air. On the second deposit, the same IEM solution with a composition of 15.1% water, 18.4% ethanol, and 4.2% solids was applied to the top surface of the ePTFE membrane 8 using a drop-coating method, with a theoretical wetting coating thickness of 1.5 mils (38.1 μm). This composite material was again dried in a convection oven at 165°C with air. The composite membrane is completely closed and has an IEM layer on each side of the microporous polymer substrate. The resulting composite membrane has a thickness of 23.8 μm at 0% RH.
[0270] Embodiment 5.2 of the present invention
[0271] Example 5.2 of the present invention was prepared according to the same process as described in Example 4.2 of the present invention, except that different materials were used. The first ePTFE membrane 5 (with a unit area mass of 4.5 g / m³) was used. 2 The first ePTFE membrane has a thickness of 23 μm, an apparent density of 0.20 g / cc, and a bubble point of 55.8 psi, while the second ePTFE membrane has a mass per unit area of 10.4 g / m³. 2 A microporous polymer structure with a thickness of 62.2 μm, an apparent density of 0.16 g / cc, and a bubble point of 56.2 psi was used as the two reinforcing layers. PSFA solution was used as the IEM (EW = 810 g / mol equivalent SO3). -(Purchased from Asahi Glass Co., Ltd., the solution composition was 32.2% water, 49.6% ethanol, and 18.2% solids). A drop-coating method was used as the first deposit, with a theoretical wetted coating thickness of 9 mils (228.6 μm). While the coating was still wet, the first ePTFE membrane 5 and the second ePTFE membrane 7, previously confined to a metal frame, were laminated onto the coating. Afterward, the IEM solution was drawn into the pores of both ePTFE membranes. This composite material was then dried in a convection oven at 165°C with air. On the second deposit, an IEM solution with the same EW composition of 18.4% water, 73.3% ethanol, and 8.3% solids was applied to the top surfaces of the two ePTFE membranes 5 and 7 using a drop-coating method, with a theoretical wetted coating thickness of 4 mils (101.6 μm). This composite material was again dried in a convection oven at 165°C with air. The multilayer composite membrane is completely closed and has an IEM layer on each side of two completely closed microporous polymer structures in contact with each other. The resulting composite membrane has a thickness of 24.1 μm at 0% RH.
[0272] Embodiment 5.3 of the present invention
[0273] Example 5.3 of the present invention was prepared according to the following procedure: First, the microporous polymer structure of three ePTFE membranes 5 (mass per unit area of 4.5 g / m³) was prepared. 2 (The thickness is 23 μm, the apparent density is 0.20 g / cc, and the bubble point is 55.8 psi) and ePTFE is stretched to eliminate wrinkles, and one is confined to the top of the other touching the metal frame. Next, IEM solution (EW = 810 g / mol equivalent SO3) is used. - The first deposit (purchased from Asahi Glass Co., Ltd., with a solution composition of 32.2% water, 49.6% ethanol, and 18.2% solids) was coated onto the top side of the polymer substrate (backing layer). The substrate (purchased from Daicel Value Coating Ltd., Japan) contained a protective layer of PET and a cyclic olefin copolymer (COC), oriented such that the COC side was on top. Coating was performed using a drop strip, with a theoretical wetted coating thickness of 9 mils (228.6 μm). While the coating was still wet, three layers of the three ePTFE membranes previously confined to the metal frame were stacked onto the coating, after which the IEM solution was drawn into the pores. The multilayer composite was then dried in a convection oven at 165°C with air. After drying, the microporous polymer matrix became completely absorbed by the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer matrix and the polymer substrate. On the second sediment, the IEM solution (EW = 710 g / mol equivalent SO3) -(Purchased from Asahi Glass Co., Ltd., the solution composition was 18.4% water, 73.3% ethanol, and 8.3% solids). The coating was applied to the top surface of the composite material (the surface opposite the polymer substrate) using a drop-down coating method, with a theoretical wettable coating thickness of 2 mils (50.8 μm). The multilayer composite was then dried again at 165°C, at which point it became largely transparent, indicating complete impregnation of the microporous polymer matrix. The multilayer composite film was completely closed and had an IEM layer on each side of the contacting microporous polymer matrix. The resulting multilayer composite film had a thickness of 24.2 μm at 0% RH.
[0274] Embodiment 5.4 of the present invention
[0275] Example 5.4 of the present invention was prepared according to the same process as described in Example 4.2 of the present invention, except that different materials were used. The first ePTFE membrane 9 (with a unit area mass of 9.9 g / m²) was used. 2 A second ePTFE membrane 9, made of the same material (with a thickness of 23 μm, an apparent density of 0.43 g / cc, and a bubble point of 130 psi), was used as a microporous polymer structure. PSFA solution was used as the IEM (EW = 810 g / mol equivalent SO3). - (Purchased from Asahi Glass Co., Ltd., the solution composition was 26.0% water, 55.0% ethanol, and 19% solids) and applied as a first deposit using a drop bar coating to the top side of a polymer substrate (backing material), with a theoretical wetting coating thickness of 9 mils (228.6 μm). While the coating was still wet, a first ePTFE membrane 9 and a second ePTFE membrane 9, previously confined to a metal frame, were laminated onto the coating. Afterward, the IEM solution was drawn into the pores of both ePTFE membranes. The composite material was then dried in a convection oven at 165°C with air. On the second deposit, an IEM solution with the same EW composition of 18.4% water, 73.3% ethanol, and 8.3% solids was applied as a drop bar coating to the top surface of the composite material, with a theoretical wetting coating thickness of 2 mils (50.8 μm). This multilayer composite material was then dried in a convection oven at 165°C with air. The resulting multilayer composite membrane is completely closed and has an IEM layer on each side of the two completely closed microporous polymer structures in contact with each other. The resulting composite membrane has a thickness of 24.0 μm at 0% RH.
[0276] Series 6
[0277] Comparative Example 6.1
[0278] Comparative Example 6.1 was prepared according to the same process as described in Comparative Example 1.1, except that different materials were used. An ePTFE membrane 10 (with a unit area mass of 29.5 g / m³) was used. 2A 137 μm thick, 0.22 g / cc apparent density, and 43.5 psi bubble point were used as the microporous polymer structure. PSFA solution was used as the IEM (EW = 1110 g / mol equivalent SO3). - (Purchased from DuPont EI, the solution composition was 38% water, 41.8% ethanol, and 20.2% solids) applied as a first deposit to the top side of a polymer substrate (backing layer) using a drop coater, with a theoretical wetting coating thickness of 10 mils (254 μm). While the coating was still wet, 10 layers of the ePTFE membrane previously confined to a metal frame were stacked onto the coating, after which the IEM solution was drawn into the pores. The composite was then dried in a convection oven at 165°C with air. On the second deposit, the same IEM solution with a composition of 26% water, 64.2% ethanol, and 9.8% solids was applied as a drop coat to the top surface of the composite, with a theoretical wetting coating thickness of 3 mils (76.2 μm). This composite was then dried in a convection oven at 165°C with air. The resulting composite membrane was completely closed and had an IEM layer on each side of the microporous polymer substrate. The resulting composite membrane has a thickness of 38.8 μm at 0% RH.
[0279] Embodiment 6.2 of the present invention
[0280] Example 6.2 of the present invention was prepared according to the following process: ePTFE membrane 7 (with a unit area mass of 10.4 g / m³) was prepared. 2 A microporous polymer structure with a thickness of 62.2 μm, an apparent density of 0.16 g / cc, and a bubble point of 56.2 psi was used as the reinforcing layer. PSFA solution was used as the IEM (EW = 1110 g / mol equivalent SO3). -(Purchased from DuPont EI, the solution composition was 24.4% water, 56.6% ethanol, and 19.0% solids) was coated onto the top side of a polymer substrate (backing layer). The polymer substrate (purchased from Daicel Value Coating Ltd., Japan) contained a protective layer of PET and a cyclic olefin copolymer (COC), oriented such that the COC side was on top. Coating was performed using a drop bar, with a theoretical wetted coating thickness of 5 mils (127 μm). While the coating was still wet, a first ePTFE membrane 7, confined to a metal frame, was laminated onto the coating, after which the IEM solution was drawn into the pores. The composite was then dried in a convection oven at 125°C with air. After drying, the microporous polymer structure (ePTFE membrane 7) became fully absorbed by the IEM. A second deposit of the same IEM solution was applied to the top surface of the composite (the surface opposite the polymer substrate) using a drop bar, with a theoretical wetted coating thickness of 5 mils (127 μm). While the coating is still wet, a second ePTFE membrane 7, previously confined to the metal frame, is laminated onto the coating. Following this, the IEM solution is drawn into the pores. The composite material is then dried in a convection oven at 125°C with air. A third deposit of the same IEM solution is applied to the top surface of the composite material using a drop bar, with a theoretical wetting coating thickness of 5 mils (127 μm). While the coating is still wet, a third ePTFE membrane 7, previously confined to the metal frame, is laminated onto the coating. Following this, the IEM solution is drawn into the pores. The composite material is then dried in a convection oven at 125°C with air. A fourth deposit of a PSFA solution with the same IEM and EW (solution composition: 20.0% water, 76.0% ethanol, 4.0% solids) is applied to the top surface of the composite material using a drop bar, with a theoretical wetting coating thickness of 5 mils (127 μm). The multilayer composite material is then dried in a convection oven at 165°C with air. The multilayer composite membrane is completely closed and has an IEM layer on each side and between each of the three completely closed microporous polymer layers spaced at a distance d of approximately 1 μm. The resulting composite membrane has a thickness of 38.6 μm at 0% RH.
[0281] Table 1 (Figure 11) presents the properties of the composite membranes of the embodiments. Table 2 (Figure 12) presents the properties of the microporous polymer structure used in the composite membranes. Improvements in puncture resistance are as follows: Figure 10 As shown, it displays a comparison graph of the average failure pressure of comparable composite membranes with the average failure pressure of the composite membrane of the present invention, plotted relative to the normalized content (μm) of the microporous polymer structure in each composite membrane. See also Figure 10Each data point (psi) associated with the mean failure pressure data is relative to the normalized content of the microporous polymer structure of each series of embodiments, as described in more detail below.
[0282] Results Discussion
[0283] Series 1 (drawn as) Figure 10 The 8 μm A) refers to Prior Art Example 1, which corresponds to Example 11.2 of WO2018 / 232254, the entire text of which is incorporated herein by reference. Series 1 also includes two comparative examples. The composite membranes have a similar thickness at 0% RH, approximately 8 μm. Prior Art Example 1 has two reinforcing layers comprising ePTFE as a microporous polymer structure arranged in contact with each other, while Comparative Examples 1.1 and 1.2 have a single reinforcing ePTFE layer. In Prior Art Example 1 and Comparative Example 1.1, the ePTFE content (expressed as the mass of ePTFE per unit area of the composite membrane) is comparable (as shown in Table 1, the total mass of ePTFE per unit area of the composite membrane is approximately 6 g / m²). 2 Figure 1 shows the normalized total content of the microporous polymer structure, which is approximately 2.5 μm. Comparative Example 1.2 has a lower ePTFE content (3.9 g / m²) in a single reinforcing layer. 2 Or 1.7 μm of normalized total ePTFE content. All three embodiments provided a poor mean failure pressure well below 150 psi. Therefore, these composite membranes are susceptible to puncture by components of electrochemical devices (e.g., redox flow cells) after device assembly.
[0284] Series 2 (drawn as) Figure 10 The 8 μm B in this series includes Prior Art Example 2 (which corresponds to Example 7.3 of WO2018 / 232254), having two ePTFE reinforcement layers separated by an inner layer of non-reinforced ion exchange material. This series also includes Comparative Example 2.1, which has a single ePTFE reinforcement layer. In this series, the composite membrane also has a thickness of approximately 8 μm at 0% RH. Prior Art Example 2 (6.1 g / m³) 2 Or the total ePTFE content in the standardized total ePTFE content (2.7 μm) was higher than that in Comparative Example 2.1 (4.5 g / m²). 2 Or 2 μm of normalized total ePTFE content). Both composite membranes presented exhibited a poor mean failure pressure of less than 150 psi. Therefore, these composite membranes are susceptible to puncture by components of electrochemical devices (e.g., redox flow cells) after device assembly.
[0285] Series 3 (drawn as) Figure 10The 15 μm A) includes Comparative Example 3.1 with a single ePTFE reinforcement layer and two embodiments of the invention with two ePTFE reinforcement layers. The membrane has a comparable thickness of about 15 μm at 0% RH. Although Comparative Example 3.1 (10.4 g / m 2 Alternatively, the total ePTFE content (standardized total ePTFE content of 4.6 μm) is greater than that of Example 3.2 of this invention (7.8 g / m). 2 Or the standardized total ePTFE content of 3.6 μm and 3.3 (9 g / m²). 2 Or a normalized total content of 4 μm ePTFE), but the mean failure pressure of Comparative Example 1 was unacceptable and below 150 psi, while both of these embodiments of the present invention have a significantly improved mean failure pressure above 150 psi.
[0286] Series 4 ( Figure 10 The diagram shows three embodiments of the invention, illustrated as 15 μm (B), including two ePTFE reinforcement layers. Figure 10 In this diagram, this series is also plotted relative to Comparative Example 4.1 (the same sample as Comparative Example 3.1), since all composite membranes have a thickness of approximately 15 μm at 0% RH. These three samples of the present invention were prepared in the same manner and they have the same amount of ePTFE (9 g / m³) distributed across both reinforcing layers. 2 Or the standardized total ePTFE content of 4 μm). These three embodiments of the invention, as well as embodiment 3.2 of the invention from series 3 (which also has the same total ePTFE content (9 g / m),) 2 All of them had a comparable mean failure pressure above 150 psi, unlike Comparative Examples 3.1 / 4.1, which had an unacceptable mean failure pressure below 150 psi, despite having a larger total ePTFE content (10.4 g / m³). 2 In this series, it can be seen that the separation between the reinforcing layers does not lead to a significant difference in the mean failure pressure.
[0287] Series 5 ( Figure 10 (Drawn as 25 μm) has: a comparative example 5.1 (with a total ePTFE content of 18 g / m²) 2 (A single reinforced ePTFE layer with a standardized total ePTFE content of 8 μm), Examples 5.1 and 5.3 of the present invention (two reinforced ePTFE layers in direct contact), and Example 5.2 of the present invention (three reinforced ePTFE layers in direct contact). All of these composite membranes have a comparable thickness of approximately 25 μm and a density of approximately 13.5 g / m³. 2 Approximately 20g / m 2The total ePTFE content (standardized total ePTFE content is 6 to 8.8 μm). For example... Figure 10 As shown, these thicker films exhibit improved mean failure pressure compared to embodiments of the invention in series 3 and 4. It is not intended to limit us to theory, but the improved mean failure pressure could be due to an increase in the total ePTFE content in the film. Furthermore, Comparative Example 5.2, with three ePTFE layers, shows a significantly improved mean failure pressure compared to Examples 5.1 and 5.3 (which have comparable total ePTFE content distributed across two rather than three reinforcing layers). All embodiments of the invention in this series exhibit superior mean failure pressure compared to Comparative Example 5.1 (which has a total ePTFE content distributed across a single reinforcing layer and a total content comparable to that of Example 5.4).
[0288] Finally, Series 6 ( Figure 10 (Drawn as 41 μm) has: A comparative example 6.1 (with a total ePTFE mass of approximately 29.5 g / m² per unit area composite membrane) has: 2 The single reinforced ePTFE layer), and Embodiment 6.2 of the present invention (having three reinforced ePTFE layers and having approximately 31.2 g / m³). 2 The total ePTFE mass per unit area of the composite membrane is [not specified]. The membrane has a comparable thickness of approximately 40 μm at 0% RH and a similar density-normalized total ePTFE content of approximately 13 μm. Due to the high thickness and ePTFE content, each sample exhibits a mean failure pressure well above 150 psi. However, sample 6.2 of the present invention shows a significant improvement over comparative example 6.1, as none of the five samples of 6.2 experienced test failure at test levels up to 419 psi, and the maximum observable mean failure pressure recorded was >419 psi.
[0289] Surprisingly, these data show that for a given amount of microporous polymer structure in the composite membrane, distributing the microporous polymer structure in at least two reinforcing layers results in a significantly improved mean failure pressure compared to distributing the same amount of microporous polymer structure in a single reinforcing layer. However, this observation only occurred in membranes with a minimum thickness of approximately 10 μm at 0% RH. As shown in Series 1 and 2, composite membranes with a thickness of approximately 8 μm at 0% RH exhibited unacceptable mean failure pressures regardless of the number of reinforcing layers. Furthermore, for comparable total amounts of microporous polymer structure, increasing the number of reinforcing layers containing microporous polymer structure (e.g., from one layer to two layers or from two layers to three layers) significantly improved the mean failure pressure, as shown in Series 5 and 6. Finally, for similar composite membrane configurations (in terms of the number of reinforcing layers containing microporous polymer structure), increasing the total amount of microporous polymer structure in the composite membrane improved the mean failure pressure. Therefore, the composite membranes according to this disclosure are highly desirable because they exhibit excellent resistance to puncture of electrochemical device components after device fabrication without compromising membrane performance.
[0290] While the invention has been described in detail, modifications falling within its spirit and scope will be readily apparent to those skilled in the art. It is understood that aspects of the invention, as well as the various embodiments and features set forth in the foregoing and / or appended claims, can be combined or interchanged in whole or in part. In the foregoing description of the various embodiments, those referred to as "another embodiment" can be suitably combined with other embodiments, as will be apparent to those skilled in the art. Furthermore, those skilled in the art will understand that the foregoing description is merely exemplary and is not intended to limit the scope of the invention.
Claims
1. A composite membrane for use in an electrochemical device, comprising: a) at least two reinforcing layers, each of the at least two reinforcing layers comprising a microporous polymer structure; as well as b) An ion exchange material (IEM) that is at least partially absorbed into the microporous polymer structure of the at least two reinforcing layers and thereby closes the microporous polymer structure. The composite membrane has a thickness of at least 10 µm at 0% RH; and The normalized total content of the microporous polymer structure in the composite membrane is at least 3.5 µm, and the normalized total content of the microporous polymer structure is calculated by the following equation: Where mps1 is microporous polymer structure 1, mps2 is microporous polymer structure 2, and mpsN is microporous polymer structure N, if there are N different types of microporous polymer structures in the composite membrane.
2. The composite membrane as described in claim 1, wherein, The at least two reinforcing layers have the same composition, or the at least two reinforcing layers have different compositions.
3. The composite membrane as described in claim 1 or 2, wherein, The microporous polymer structure includes at least one fluorinated polymer, or wherein the microporous polymer structure includes at least one fluorinated polymer and the fluorinated polymer is: polytetrafluoroethylene (PTFE), poly(ethylene cotetrafluoroethylene) (EPTFE), expanded polytetrafluoroethylene (ePTFE), polyvinylidene fluoride (PVDF), expanded polyvinylidene fluoride (ePVDF), expanded poly(ethylene cotetrafluoroethylene) (eEPTFE), or a mixture thereof.
4. The composite membrane as described in claim 3, wherein, Fluorinated polymers are perfluorinated expanded polytetrafluoroethylene (ePTFE), or wherein... The fluorinated polymer is perfluorinated expanded polytetrafluoroethylene (ePTFE), and at least one of the following: The composite membrane has a strength of at least 5.5 g·m³. -2 The total content of the microporous polymer structure is calculated based on the total mass per unit area of all reinforcing layers present in the composite membrane. The composite membrane has a strength of 5.5 g·m³. -2 Up to 80 g·m -2 The total content of the microporous polymer structure is calculated based on the sum of the mass per unit area of all reinforcing layers present in the composite membrane.
5. The composite membrane as described in claim 1 or 2, wherein, The microporous polymer structure includes hydrocarbon polymers, or wherein the microporous polymer structure includes hydrocarbon polymers and hydrocarbon polymers include polyethylene, polypropylene, polycarbonate, polystyrene, or mixtures thereof.
6. The composite membrane as described in claim 1 or 2, wherein, It has one of the following: The at least two reinforcing layers are in direct contact; or The composite membrane includes at least one inner layer of ion exchange material between the at least two reinforcing layers.
7. The composite membrane as described in claim 1 or 2, wherein, The distance between the at least two reinforcing layers is d.
8. The composite membrane as described in claim 7, wherein, It has at least one of the following: At 0% RH, the spacing d ranges from 0.1 µm to 20 µm; At 0% RH, the spacing d is 0.5 µm to 5 µm.
9. The composite membrane as described in claim 1 or 2, wherein, It has one of the following: Ion exchange materials consist of more than one layer of ion exchange material. In this configuration, the ion exchange material layer is formed from the same ion exchange material; or the ion exchange material comprises more than one layer of ion exchange material. The first layer of the ion exchange material is formed by a second layer of ion exchange material that is different from the second layer of the ion exchange material.
10. The composite membrane as described in claim 1 or 2, wherein, It has at least one of the following: The microporous polymer structure completely absorbed the ion exchange material; Each of the at least two reinforcing layers has a microporous polymer structure having a first surface and a second surface, and wherein an ion exchange material is formed on at least one of the first surface or the second surface of each of the at least two reinforcing layers.
11. The composite membrane as described in claim 1 or 2, wherein, Each of the at least two reinforcing layers has a microporous polymer structure having a first surface and a second surface, and The microporous polymer structure absorbs most of the ion exchange material, but there are areas of the microporous polymer structure that do not absorb the material or are not sealed, such as the first surface closest to at least one of the at least two reinforcing layers, the second surface closest to at least one of the at least two reinforcing layers, or the areas of the microporous polymer structure that do not absorb the material.
12. The composite membrane as described in claim 11, wherein, 90% of the microporous polymer structure of the at least two reinforcing layers is sealed by ion exchange material.
13. The composite membrane as described in claim 1 or 2, wherein, The average equivalent volume of ion exchange materials is between 240 cc / mol equivalent and 870 cc / mol equivalent, or wherein... The average equivalent volume of the ion exchange material is from 350 cc / mol equivalent to 475 cc / mol equivalent, or wherein the average equivalent volume of the ion exchange material is from 240 cc / mol equivalent to 650 cc / mol equivalent.
14. The composite membrane as described in claim 1 or 2, wherein, Ion exchange materials contain at least one ionomer, or wherein, The ion exchange material comprises at least one ionomer, and at least one of the following: The at least one ionomer includes a proton-conducting polymer; The at least one ionomer has a density of not less than 1.9 g / cc at 0% relative humidity.
15. The composite membrane as described in claim 1 or 2, wherein, It has one of the following: The composite membrane has the following thicknesses at 0% RH: 10 µm to 115 µm, or 10 µm to 90 µm, or 10 µm to 40 µm, or 10 µm to 30 µm, or 10 µm to 20 µm; The composite membrane has a thickness of 15 µm at 0% RH; The composite membrane has a thickness of 25 µm at 0% RH.
16. The composite membrane as described in claim 1 or 2, wherein, When measured using the mean puncture pressure failure test described herein, the composite membrane exhibits a mean failure pressure ranging from 150 psi to 500 psi.
17. The composite membrane of claim 1 or 2, further comprising at least one backing layer removably attached to one or more outer surfaces of the composite membrane.
18. A membrane electrode assembly for an electrochemical device, comprising: At least one electrode; as well as The composite film as described in claim 1 or 2 that is in contact with the at least one electrode.
19. The membrane electrode assembly as claimed in claim 18, wherein, It has at least one of the following: The composite film is attached to the at least one electrode; The at least one electrode includes a porous layer; The at least one electrode comprises carbon fiber.
20. The membrane electrode assembly as claimed in any one of claims 18 or 19, wherein, The membrane electrode assembly is a redox flow cell membrane electrode component, which includes: A first electrode having a first surface and a second surface; A second electrode having a first surface and a second surface; as well as The composite film having a first surface and a second surface as described in any one of claims 1 or 2, The second surface of the first electrode is in contact with the first surface of the composite film, and the first surface of the second electrode is in contact with the second surface of the composite film.
21. The membrane electrode assembly as claimed in claim 20, wherein, It has at least one of the following: The redox flow cell membrane electrode assembly includes a first electrode layer attached to a first surface of a composite membrane and a second electrode layer attached to a second surface of the composite membrane. The first electrode layer and / or the second electrode layer are porous layers with a pore size of 1 to 200 µm.
22. The membrane electrode assembly as claimed in claim 18 or 19, wherein, The at least one electrode is selected from felt, paper, or woven materials.
23. The membrane electrode assembly as described in claim 20 or 22, wherein, It has at least one of the following: The first and / or second electrodes are carbon / platinum electrodes having ionomers or wherein... The electrode contains an alloy with ionomers; The first and / or second electrodes contain doped carbon fibers.
24. The membrane electrode assembly as claimed in claim 18 or 19, wherein, Membrane electrode assembly is a fuel cell membrane electrode module, which includes: The composite membrane as described in claim 1 or 2, wherein the composite membrane has a first surface and a second surface; The first layer of electrode catalyst adhered to the first surface of the composite membrane; and The second layer of electrode catalyst adheres to the second surface of the composite membrane.
25. The membrane electrode assembly as claimed in claim 24, wherein, It has at least one of the following: The first and second layers of the electrode catalyst are nanoporous layers with pore sizes up to 100 nm. The first and second layers of the electrode catalyst comprise: One or more ionomers; Catalyst support, such as carbon black; and platinum.
26. The membrane electrode assembly of claim 18 or 19, wherein, The membrane electrode assembly is an electrolyzer electrode assembly, which includes: The composite membrane as described in claim 1 or 2, wherein the composite membrane has a first surface and a second surface. The first layer of electrode catalyst adhered to the first surface of the composite membrane; and The second layer of electrode catalyst adheres to the second surface of the composite membrane.
27. The membrane electrode assembly of claim 24 or 26, wherein, A layer of platinum or ruthenium catalyst adheres to the composite membrane.
28. A fuel cell comprising a composite membrane as described in claim 1 or 2, or a membrane electrode assembly as described in claim 18, 19, 24, or 27.
29. A redox flow cell comprising a composite membrane as described in claim 1 or 2, or a membrane electrode assembly as described in claim 18 or 19.
30. An electrolytic cell comprising a composite membrane as described in claim 1 or 2, or a membrane electrode assembly as described in claim 18 or 19.
Citation Information
Patent Citations
Copolymers of tetrafluoroethylene and perfluorinated sulfonyl monomers and membranes made therefrom
US5463005A
Porous PTFE materials and articles produced therefrom
US8757395B2
Highly reinforced ionomer membranes for high selectivity and high strength
WO2018232254A1
Highly reinforced ionomer membranes for high selectivity and high strength
CN110741498A
